Alkali-treated fabric / fiber / staple fibers with improved antimicrobial properties

Through alkaline composition treatment, especially mercerizing treatment, the performance of antimicrobial fibers is significantly improved, and the problem of difficulty in improving the performance of AM/AV fibers in the prior art is solved, and efficient improvement of antimicrobial performance and mechanical strength is achieved.

CN119173660APending Publication Date: 2024-12-20ASCEND PERFORMANCE MATERIALS OPERATIONS LLC
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202380039018.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-10
Filing Date
2023-05-10
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to significantly improve the performance of antimicrobial (AM/AV) fibers and fabrics with antimicrobial efficacy by conventional merceration methods, especially without adding additional AM/AV compounds.

Method used

The base fibers are treated with an alkali composition, including merceration treatment, by contacting the fibers with alkali solution to improve the performance of the AM/AV fibers, to form treated fibers with improved AM/AV efficacy. The process may include a polymer such as polyamide and processed at a certain temperature and residence time, possibly including a washing and neutralization step.

Benefits of technology

The antimicrobial properties of the fibers are significantly improved, such as logarithmic reductions in Klebsiella pneumoniae, E. coli and Staphylococcus aureus, without the need for additional AM/AV compounds, improving the mechanical strength and appearance characteristics of the fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123005960000421
    Figure BDA0005123005960000421
  • Figure BDA0005123005960000431
    Figure BDA0005123005960000431
Patent Text Reader

Abstract

The present disclosure relates to a method of producing a treated AM / AV fiber comprising treating a base AM / AV fiber with a base composition to form a treated AM / AV fiber, the base AM / AV fiber comprising a polymer composition comprising a polymer and an AM / AV compound. The treated AM / AV fibers exhibit a logarithmic reduction of Klebsiella pneumoniae of greater than 1.5 as determined by ISO 20743: 2013.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references

[0002] This application is related to and claims priority to U.S. Provisional Patent Application No. 63 / 340,315 filed on May 10, 2022, which is incorporated herein by reference.

[0003] field

[0004] The present disclosure relates to antimicrobial fabrics / fibers / staple fibers having improved antimicrobial efficacy.

[0005] background

[0006] Conventional base fabrics / fibers / staple fibers have long faced appearance-related problems. Exemplary problems include unswollen fibers, poor dye uptake, and poor gloss. The appearance of a fabric is obviously an important factor in applications where the fabric is used, such as clothing. Therefore, many efforts have been made to treat base fabrics to improve their appearance-related characteristics.

[0007] One such treatment is an alkali treatment of the base fabric, which is known in the industry as "mercerization". This process removes curl from the (cotton) fiber structure and swells the fibers of the fabric, for example making the fibers rounder, which improves the feel of the fabric and makes it appear more lustrous. In cotton-based fabrics, mercerization is also known to improve the mechanical strength of the fabric.

[0008] U.S. Publication No. 20140308865A1 discloses a core-spun yarn in which the core is a stretchable filament and is surrounded by a sheath of polytrimethylene terephthalate-based staple fibers combined with a second staple fiber. Fabrics are made using the core-spun yarn. Fabrics made from the core-spun yarn are highly stretchable, have high dimensional stability, low growth, and high recovery.

[0009] U.S. Patent No. 9,982,372 B2 discloses an article comprising a woven fabric, the woven fabric comprising warp yarns and weft yarns, wherein at least one of the warp yarns or weft yarns comprises: (a) a core-spun elastic base yarn having a certain denier and comprising staple fibers and an elastic fiber core; and (b) a separate control yarn selected from a monofilament yarn, a multifilament yarn, a composite yarn, and combinations thereof; having a denier of greater than 0 to about 0.8 times the denier of the core-spun elastic base yarn; wherein the woven fabric comprises (1) a ratio of core-spun base yarn warp yarns to control yarn warp yarns of up to about 6:1; or (2) a ratio of core-spun base yarn weft yarns to control yarn weft yarns of up to about 6:1; or (3) a ratio of core-spun base yarn warp yarns to control yarn warp yarns of up to about 6:1; and a ratio of core-spun base yarn weft yarns to control yarn weft yarns of up to about 6:1.

[0010] In addition, polymer compositions (and fabrics made therefrom) are disclosed. Such compositions generally comprise a polymer and an AM / AV compound. For example, U.S. Publication No. 20210277234A1 discloses a polymer composition having antimicrobial properties, the composition comprising 50 wt % to 99.99 wt % of a polymer, 10 wppm to 900 wppm of zinc, less than 1000 wppm of phosphorus, and less than 10 wppm of a coupling agent and / or surfactant, wherein the zinc is dispersed in the polymer; and wherein the fiber formed by the polymer composition exhibits a Klebsiella pneumoniae log reduction of greater than 0.90 as measured by ISO 20743:2013 and / or a log reduction of greater than 1.5 of Escherichia coli as measured by ASTM E3160 (2018).

[0011] Even in view of these references, there remains a need for a process for producing compositions / fibers / fabrics having improved AM / AV efficacy, preferably wherein the improvement is derived from process parameters and wherein the use of additional AM / AV compounds is avoided.

[0012] Overview

[0013] In some cases, the present disclosure relates to a method for producing an improved, treated AM / AV fiber, comprising treating (e.g., mercerizing) a base fiber, such as a base AM / AV fiber, with an alkaline composition to form an improved AM / AV fiber. The base fiber optionally comprises a polymer composition comprising a polymer, such as a polyamide such as PA6, PA 6,6, PA 6,10 or PA6,12 or a combination thereof, and an AM / AV compound, and may be a staple fiber. The treatment may include treating the base AM / AV fiber to form a treated AM / AV fiber and treating a companion fiber to form a treated companion fiber. The companion fiber may comprise a different polymer composition comprising a different polymer, such as a natural fiber, preferably cotton and / or cellulose. The improved AM / AV fiber may comprise a base fiber embedded with ionic zinc (Zn 2+) of a polyamide polymer matrix. The improved AM / AV fiber may exhibit a Klebsiella pneumoniae log reduction of greater than 1.5 as determined by ISO20743:2013 and / or a Escherichia coli log reduction of greater than 1.5 as determined by ASTM E3160 (2018), and / or a Staphylococcus aureus log reduction of greater than 3.0 as determined by ISO20743:2013. The treatment may improve the AM / AV performance of the fiber relative to the base fiber, and may include contacting the base fiber with an alkaline solution having a concentration of 5% to 50% at a residence time of 5 seconds to 30 minutes and / or a temperature of 5°C to 50°C. The treatment may further include a washing and / or neutralization step. The polymer composition may contain 5wppm to 20,000 AM / AV compounds. The polymer may have a relative viscosity of less than 100 (as measured by the formic acid method), and may be hydrophilic and / or hygroscopic, and capable of absorbing greater than 1.5% by weight of water based on the total weight of the polymer.

[0014] In some cases, the present disclosure relates to treated AM / AV fibers comprising a polymer and an AM / AV compound, wherein the treated AM / AV fibers are alkali treated with an alkali composition, wherein the AM / AV fibers exhibit a Klebsiella pneumoniae log reduction of greater than 1.5 as measured by ISO 20743:2013. The alkali composition may have a concentration of 5% to 50%. The treated AM / AV fibers may comprise PA6, PA 6,6, PA 6,10, or PA 6,12, or a combination thereof and may have a relative viscosity of 20 to 60 as measured by the formic acid method.

[0015] Details

[0016] introduction

[0017] As mentioned above, it is known to treat a base fabric of cotton fibers with an alkali composition, such as mercerizing, to improve its appearance-related and / or performance-related characteristics. This method removes curls from the (cotton) fiber structure and swells the fibers of the fabric, such as making the fibers rounder, which improves the feel of the fabric and makes it look more shiny. In cotton-based fabrics, mercerizing is also known to improve the mechanical strength of the fabric. AM / AV compositions / fibers / fabrics are also known. However, there is little or no disclosure in the references that teaches that alkali treatments of base fabrics / fibers (comprising AM / AV compounds), such as mercerizing, will have any effect on the AM / AV efficacy.

[0018] It has now been found that treating a base fabric / fiber comprising an AM / AV compound with an alkali composition surprisingly provides a significant improvement in AM / AV effectiveness. This is particularly surprising because the reference does not mention the ability of mercerizing to improve this property. In other words, mercerizing is not known to improve AM / AV effectiveness, and there is little or no instruction for conventional mercerizing processes to use fabrics comprising AM / AV compounds. And since mercerized fabrics are generally free of AM / AV compounds, such as zinc compounds, there is no instruction that such improvements are inherent in the prior art. Importantly, mercerizing is used to solve a completely different set of problems, such as unswollen fibers, poor dye uptake, and poor gloss properties. When using the method described herein, an unexpected improvement in AM / AV effectiveness is obtained without the need to use additional (or higher amounts) AM / AV compounds that may increase the cost and other complexities of the production method in some cases.

[0019] Methods for producing improved AM / AV fibers / fabrics

[0020] The present disclosure relates to a method for producing improved AM / AV fibers (or fabrics containing such fibers). The method includes the step of treating a base fiber or a base fabric with an alkali composition to form an improved AM / AV fiber / fabric having improved AM / AV efficacy (compared to the base fiber / fabric). The base fiber / fabric comprises an AM / AV polymer composition (or is made of an AM / AV polymer composition). Importantly, the AM / AV compound is present in the base fiber / fabric before the alkali treatment. For example, the AM / AV fiber may exhibit a log reduction of Klebsiella pneumoniae greater than 1.5 as determined by ISO20743:2013 and / or a log reduction of Escherichia coli greater than 1.5 as determined by ASTM E3160 (2018), and / or a log reduction of Staphylococcus aureus greater than 3.0 as determined by ISO20743:2013.

[0021] The treatment may be mercerization, which is a treatment invented by John Mercer in 1844 and is well known in the industry. In some cases, alkaline treatments, such as mercerization, contribute to or provide improved AM / AV performance. In some cases, the method may further include a washing and / or neutralization step after the alkaline treatment.

[0022] The fabric (or yarns comprising the fabric) may comprise base fibers and, in some cases, may comprise multiple types of fibers (see discussion below regarding polymer types). In some cases, the fabric may comprise polyamide fibers and may further comprise companion fibers, such as cotton. Both the base fibers and the companion fibers may be alkali treated, such as to form treated AM / AV fibers and treated companion fibers. Additional materials for companion fibers are disclosed herein.

[0023] In some cases, the base fibers include AM / AV fibers comprising an AM / AV compound (and optionally a polyamide) and companion fibers comprising a different polymer or fiber, such as a natural fiber, preferably cotton and / or cellulose (and optionally containing little or no AM / AV compound).

[0024] In some cases, the fabric (or yarn) comprises all polymer, such as all nylon, and contains no companion fibers, such as no cotton.

[0025] In some cases, the fabric (or yarn) comprises less than 99 wt% AM / AV base fibers, such as less than 90 wt%, less than 80 wt%, less than 70 wt%, less than 60 wt%, less than 50 wt%, less than 40 wt%, less than 30 wt%, less than 20 wt%, less than 10 wt%, or less than 5 wt%. In some cases, the fabric (or yarn) comprises greater than 0.1 wt% AM / AV base fibers, such as greater than 0.5 wt%, greater than 1 wt%, greater than 5 wt%, greater than 10 wt%, greater than 20 wt%, greater than 30 wt%, greater than 40 wt%, greater than 50 wt%, greater than 60 wt%, greater than 70 wt%, greater than 80 wt%, greater than 90 wt%, or greater than 95 wt%.

[0026] In some cases, the fabric (or yarn) comprises less than 99% by weight of companion fibers, such as less than 90%, less than 80%, less than 70%, less than 60%, less than 50%, less than 40%, less than 30%, less than 20%, less than 10%, or less than 5%. In some cases, the fabric (or yarn) comprises greater than 0.1% by weight of companion fibers, such as greater than 0.5%, greater than 1%, greater than 5%, greater than 10%, greater than 20%, greater than 30%, greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, greater than 90%, or greater than 95%.

[0027] Alkali (or alkaline) treatment can vary greatly. In some cases, the treatment comprises contacting the base fiber with an alkaline solution at a certain residence time and / or at a certain temperature. In some embodiments, the concentration of the alkaline solution is 5% to 50%, such as 10% to 40%, 15% to 35%, 20% to 30%, 22% to 28%, or 24% to 26%. In terms of the lower limit, the concentration of the alkaline solution can be greater than 5%, such as greater than 10%, greater than 15%, greater than 20%, greater than 22%, or greater than 24%. In terms of the upper limit, the concentration of the alkaline solution can be less than 50%, such as less than 40%, less than 35%, less than 30%, less than 28%, or less than 26%. The alkaline solution may include an alkaline component and a solvent. The alkaline component can vary greatly, and many alkaline components are known. Examples include hydroxides, such as sodium hydroxide or lithium hydroxide. The alkaline component can also be interpreted as including carbonates, ammonia, and other alkaline compounds well known in the art. Although these may not include hydroxide ions, these are still considered for the disclosed method. The base solution can be prepared by dissolving the base component in a solvent in a stoichiometric amount appropriate to produce the desired concentration.

[0028] In some embodiments, this treatment is carried out with 5 seconds to 30 minutes, for example, 10 seconds to 25 minutes, 10 seconds to 10 minutes, 20 seconds to 20 minutes, 30 seconds to 15 minutes, 30 seconds to 10 minutes or 45 seconds to 5 minutes of residence time.With regard to the lower limit, this treatment can be carried out with greater than 5 seconds, for example, greater than 10 seconds, greater than 20 seconds, greater than 30 seconds, greater than 45 seconds, greater than 1 minute, greater than 2 minutes, greater than 3 minutes or greater than 5 minutes of residence time.With regard to the upper limit, this treatment can be carried out with less than 30 minutes, for example, less than 25 minutes, less than 20 minutes, less than 15 minutes, less than 10 minutes, less than 8 minutes, less than 5 minutes, less than 3 minutes or less than 2 minutes of residence time.

[0029] In some embodiments, the treatment is carried out at a temperature of 5° C. to 50° C., e.g., 5° C. to 40° C., 8° C. to 30° C., 10° C. to 25° C., or 15° C. to 18° C. In terms of lower limits, the treatment may be carried out at a temperature greater than 5° C., e.g., greater than 8° C., greater than 10° C., greater than 12° C., or greater than 15° C. In terms of upper limits, the treatment may be carried out at a temperature less than 50° C., e.g., less than 40° C., less than 30° C., less than 25° C., or less than 18° C.

[0030] In some cases, the base fiber can be formed into a base fabric or base material. The base fabric / fiber / material may include (or may be made of) an AM / AV polymer composition including a polymer and an AM / AV compound, such as zinc. These components are discussed in more detail herein. The manner of forming the fiber can vary greatly. Exemplary fiber formation methods include, but are not limited to, melt spinning, spunbonding, spunlace, meltblowing, electrostatic spinning, and ring spinning. Similarly, the manner of forming the fabric can vary greatly. Exemplary fabric formation methods include, but are not limited to, nonwoven production methods and weaving production methods, such as weaving, knitting. In some embodiments, these formation methods do not affect the positive impact of alkali treatment on AM / AV performance.

[0031] The overall composition of the fabric can vary widely. In some cases, the fabric includes some fibers comprising or made from an AM / AV compound (optionally using polyamide). The fabric may also include companion yarns such as cotton, spandex, PET, acrylic, etc. in some embodiments.

[0032] Other AM / AV compositions / configurations that can be treated to improve AM / AV performance are also contemplated by this specification. Examples include wet wipes, absorbent materials, and feminine hygiene products.

[0033] In addition, the use of the AM / AV composition has been shown to increase the overall hydrophilicity and / or hygroscopicity of the AM / AV material. For example, it is theorized that polymers with increased hydrophilicity and / or hygroscopicity may better attract liquids and / or capture media carrying microorganisms and / or viruses, and may also absorb more moisture, such as air, and the increased moisture content makes the polymer composition and AM / AV compound more likely to destroy, limit, reduce or inhibit the infection and / or pathogenic mechanisms of microorganisms or viruses.

[0034] The disclosed improved AM / AV fabrics can provide comfort to the user, for example due to their softness or formability, for example due to the characteristics of the fabric sheet such as fiber diameter or denier, or due to synergistic properties imparted by an alkali treatment that can provide softness. The fabric can be composed of AM / AV fibers and / or fabrics and can thus be endowed with AM / AV capabilities. Thus, the fabric sheet can prevent contact transmission of pathogens that would otherwise allow the pathogens to spread or pass through the material to the wearer.

[0035] In some embodiments, the fabric comprises a plurality of fibers having an average fiber diameter of less than 50 microns, such as less than 45 microns, less than 40 microns, less than 35 microns, less than 30 microns, less than 25 microns, less than 20 microns, less than 15 microns, less than 10 microns, or less than 5 microns. In terms of lower limits, the plurality of fibers may have an average fiber diameter greater than 1 micron, such as greater than 1.5 microns, greater than 2 microns, greater than 2.5 microns, greater than 5 microns, or greater than 10 microns. In terms of ranges, the plurality of fibers may have an average fiber diameter of 1 micron to 50 microns, such as 1 micron to 45 microns, 1 micron to 40 microns, 1 micron to 35 microns, 1 micron to 30 microns, 1 micron to 20 microns, 1 micron to 15 microns, 1 micron to 10 microns, 1 micron to 5 microns, 1.5 microns to 25 microns, 1.5 microns to 20 microns, 1.5 microns to 15 microns, 1.5 microns to 10 microns, 1.5 microns to 5 microns, 2 microns to 25 microns, 2 microns to 20 10 to 30 microns, 10 to 45 microns, 10 to 40 microns, 10 to 35 microns, and 10 to 30 microns. In some cases, fibers of this size may be referred to as microfibers.

[0036] In some embodiments, the fabric comprises a plurality of fibers having an average fiber diameter of less than 1 micron, e.g., less than 0.9 micron, less than 0.8 micron, less than 0.7 micron, less than 0.6 micron, less than 0.5 micron, less than 0.4 micron, less than 0.3 micron, less than 0.2 micron, less than 0.1 micron, less than 0.05 micron, less than 0.04 micron, or less than 0.03 micron. In terms of lower limits, the average fiber diameter of the plurality of fibers can be greater than 1 nanometer, e.g., greater than 10 nanometers, greater than 25 nanometers, or greater than 50 nanometers. In terms of ranges, the plurality of fibers can have an average fiber diameter of 1 nm to 1 micron, e.g., 1 nm to 0.9 micron, 1 nm to 0.8 micron, 1 nm to 0.7 micron, 1 nm to 0.6 micron, 1 nm to 0.5 micron, 1 nm to 0.4 micron, 1 nm to 0.3 micron, 1 nm to 0.2 micron, 1 nm to 0.1 micron, 1 nm to 0.05 micron, 1 nm to 0.04 micron, 1 nm to 0.3 micron, 10 nm to 1 micron, 10 nm to 0.9 micron, 10 nm to 0.8 micron, 10 nm to 0.7 micron, 10 nm to 0.6 micron, 10 nm to 0.5 micron, 10 nm to 0.4 micron, 1 nm to 0.3 micron, 10 nm to 0.2 micron, 10 nm to 0.1 micron, 10 nm to 0.05 micron, 10 nm to 0.04 micron, 10 nm to 0.0 0.3 micrometer, 25 nm to 1 micrometer, 25 nm to 0.9 micrometer, 25 nm to 0.8 micrometer, 25 nm to 0.7 micrometer, 25 nm to 0.6 micrometer, 25 nm to 0.5 micrometer, 25 nm to 0.4 micrometer, 25 nm to 0.3 micrometer, 25 nm to 0.2 micrometer, 25 nm to 0.1 micrometer, 25 nm to 0.05 micrometer, 25 nm to 0.04 micrometer, 25 nm to 0.03 micrometer, 50 nm to 1 micrometer, 50 nm to 0.9 micrometer, 50 nm to 0.8 micrometer, 50 nm to 0.7 micrometer, 50 nm to 0.6 micrometer, 50 nm to 0.5 micrometer, 50 nm to 0.4 micrometer, 50 nm to 0.3 micrometer, 50 nm to 0.2 micrometer, 50 nm to 0.1 micrometer, 50 nm to 0.05 micrometer, 50 nm to 0.04 micrometer, or 50 nm to 0.03 micrometer. In some cases, fibers of this size may be referred to as nanofibers.

[0037] In some cases, the fabric has a thickness of 25 microns to 500 microns, for example, 25 microns to 400 microns, 35 microns to 300 microns, or 50 microns to 275 microns. In terms of upper limits, the fabric sheet can have a thickness of less than 500 microns, for example, less than 400 microns, less than 300 microns, or less than 275 microns. In terms of lower limits, the fabric can have a thickness greater than 25 microns, for example, greater than 35 microns, greater than 50 microns, or greater than 60 microns.

[0038] It has been found that the fabric can advantageously be composed of relatively hydrophilic and / or hygroscopic materials. Polymers with increased hydrophilicity and / or hygroscopicity can better attract and retain moisture to which the AM / AV material is exposed. As discussed below, improved, for example increased, hydrophilicity and / or hygroscopicity can be achieved by employing the polymer compositions described herein. Therefore, forming fabric sheets, such as fibers, from the disclosed polymer compositions is particularly beneficial.

[0039] Physical properties

[0040] As discussed above, various layers of the improved AM / AV fibers / fabrics may benefit from increased hydrophilicity and / or hygroscopicity.

[0041] In some cases, the hydrophilicity and / or hygroscopicity of improved AM / AV fiber / fabric can be measured by saturation. In some cases, the hydrophilicity and / or hygroscopicity of a given layer of improved AM / AV fiber / fabric can be measured by its absorbable water amount (as the percentage of gross weight). In some embodiments, the layer can absorb the water greater than 1.5 wt % based on the gross weight of polymer, for example, greater than 2.0 wt %, greater than 3.0%, greater than 5.0 wt %, greater than 7.0 wt %, greater than 10.0 wt % or greater than 25.0 wt %. With regard to scope, hydrophilic and / or hygroscopic polymer can absorb the water of 1.5 wt % to 50.0 wt %, for example, 1.5 wt % to 14.0 wt %, 1.5 wt % to 9.0 wt %, 2.0 wt % to 8 wt %, 2.0 wt % to 7 wt %, 2.5 wt % to 7 wt % or 1.5 wt % to 25.0 wt %.

[0042] In some cases, the hydrophilicity and / or hygroscopicity of the improved AM / AV fiber / fabric can be measured by the water contact angle of the layer.The water contact angle is the angle formed by the interface of the surface of the layer (eg, fabric).

[0043] In some embodiments, the improved AM / AV fibers / fabrics exhibit a water contact angle of less than 90°, for example, less than 85°, less than 80°, or less than 75°. With respect to lower limits, the water contact angle of the layer may be greater than 10°, for example, greater than 20°, greater than 30°, or greater than 40°. With respect to ranges, the water contact angle of the layer may be from 10° to 90°, for example, from 10° to 85°, from 10° to 80°, from 10° to 75°, from 20° to 90°, from 20° to 85°, from 20° to 80°, from 20° to 75°, from 30° to 90°, from 30° to 85°, from 30° to 80°, from 30° to 75°, from 40° to 90°, from 40° to 85°, from 40° to 80°, or from 40° to 75°.

[0044] The improved AM / AV fibers / fabrics disclosed herein advantageously provide AM / AV properties, such as pathogen destruction properties. For example, the disclosed improved AM / AV fibers / fabrics destroy pathogens by contacting them before the pathogens have a chance to enter or contact the body. The AM / AV properties are achieved at least in part by the composition of the fibers that make up the layer. In addition to the alkaline treatment, at least one layer contains a polymer component and an AM / AV compound, such as zinc and / or copper, which is embedded in the polymer structure in some cases (but may not be a component of the polymerized copolymer). The presence of the AM / AV compound in the fiber polymer provides pathogen destruction properties together with the alkaline treatment. Therefore, the disclosed article prevents the growth or spread of pathogens from contact, otherwise the pathogens will be spread. Importantly, because the AM / AV compound can be embedded in the polymer structure, the AM / AV properties are durable and not easily worn or washed off. Therefore, the improved AM / AV fibers / fabrics disclosed herein achieve a synergistic combination of AM / AV efficacy and biocompatibility (e.g., irritation and sensitization) properties.

[0045] In some cases, the base fiber is a staple fiber. In other cases, filaments are also considered, and the method can be used to treat the base filaments in the same manner as the base fiber / fabric.

[0046] In some cases, blends of polyamide staple fibers and cotton staple fibers are contemplated.

[0047] As described above, the improved hydrophilicity and / or hygroscopicity of the improved AM / AV fibers / fabrics can be attributed to the polymer composition used to form the layer. The polymer compositions described herein, for example, exhibit improved hydrophilicity and / or hygroscopicity and are therefore particularly suitable for use in the disclosed improved AM / AV fibers / fabrics.

[0048] In some embodiments, the polymer may be specially prepared to impart increased hydrophilicity and / or hygroscopicity. For example, increased hygroscopicity may be achieved in the selection and / or modification of the polymer. In some embodiments, the polymer may be a conventional polymer, such as a conventional polyamide, that has been modified to increase hygroscopicity. In these embodiments, modification of the functional end groups on the polymer may increase hygroscopicity. For example, the polymer may be PA6,6 that has been modified to include functional end groups that increase hygroscopicity.

[0049] Performance characteristics

[0050] The performance of the improved AM / AV fibers / fabrics described herein can be evaluated using various conventional criteria.

[0051] Anti-odor performance can be measured by odor reduction as measured according to ISO 17299-3 (2014). In some embodiments, the improved AM / AV fiber / fabric exhibits an odor reduction of greater than 50%, such as greater than 60%, greater than 70%, greater than 80%, or greater than 90%. Odors can be tested using specific test chemicals, such as ammonia, acetic acid, isovaleric acid, hydrogen sulfide, indole and / or nonenal. At least one layer (or its fibers) exhibits odor reduction to one or more of these test chemicals. The disclosed fabric can exhibit an odor reduction of greater than 50%, such as greater than 60%, greater than 70%, or greater than 80%, as measured according to ISO 17299-3 (2014).

[0052] In some cases, the AM / AV performance relates to antifungal properties. The antifungal activity of the improved AM / AV fibers / fabrics can be measured by standard procedures as defined in Mod. E3160. In one embodiment, the improved AM / AV fibers / fabrics inhibit the growth (growth reduction) of Candida auris or Candida albicans by greater than 10% fungal growth, such as greater than 20%, greater than 30%, greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, greater than 90% or greater than 93%.

[0053] As described above, in some embodiments, the improved AM / AV fibers / fabrics may exhibit AM / AV activity. In some cases, the AM / AV activity may be attributed to the polymer composition and alkali treatment used to prepare the AM / AV material. For example, the AM / AV activity may be attributed to forming the improved AM / AV fibers / fabrics from the polymer composition described herein and treating them as described herein.

[0054] In some embodiments, the improved AM / AV fibers / fabrics exhibit permanent, e.g., near-permanent AM / AV properties. In other words, the AM / AV properties of the polymer composition persist for a long time, e.g., more than one day or more days, more than one week or more weeks, more than one month or more months, or more than one year or more years.

[0055] AM / AV properties may include any antimicrobial effect. In some embodiments, for example, the antimicrobial properties of the AM / AV material include limiting, reducing, or inhibiting infection by microorganisms, such as bacteria. In some embodiments, the antimicrobial properties of the AM / AV material include limiting, reducing, or inhibiting bacterial growth and / or killing bacteria. In some cases, the AM / AV material can limit, reduce, or inhibit infection and / or growth of bacteria.

[0056] The bacteria affected by the antimicrobial properties of the improved AM / AV fibers / fabrics are not particularly limited. In some embodiments, for example, the bacterium is a Streptococcus bacterium (e.g., Streptococcus pneumonia, Streptococcus pyogenes), a Staphylococcus bacterium (e.g., Staphylococcus aureus, methicillin-resistant Staphylococcus aureus (MRSA)), a Peptostreptococcus bacterium (e.g., Peptostreptococcus anaerobius, Peptostreptococcus asaccharolyticus), an Escherichia coli bacterium (e.g., Escherichia coli), or a Mycobacterium bacterium (e.g., Mycobacterium tuberculosis), a Mycoplasma bacterium (e.g., Mycoplasma adleri, Mycoplasma agalactiae, Mycoplasma agassizii, Mycoplasma amphoriforme, Mycoplasma fermentans), or a Streptococcus genus (e.g., Streptococcus pyogenes ... fermentans, Mycoplasma genitalium, Mycoplasma haemofelis, Mycoplasma hominis, Mycoplasma hyopneumoniae, Mycoplasma hyorhinis, Mycoplasma pneumoniae). In some embodiments, the antimicrobial property includes limiting, reducing or inhibiting the infection or pathogenicity mechanisms of multiple bacteria, such as a combination of two or more bacteria from the above list.

[0057] The antimicrobial activity of the improved AM / AV fiber / fabric can be measured by the standard procedure specified in ISO 20743:2013. This procedure measures the antimicrobial activity by determining the percentage of a given bacterium, such as Staphylococcus aureus, inhibited by the tested fiber. In one embodiment, the improved AM / AV fiber / fabric has an antimicrobial activity of 60% to 100%, such as 60% to 99.99999%, 60% to 99.99999%, 60% to 99.9999%, 60% to 99.999%, 60% to 99.999%, 60% to 99.99%, 60% to 99.9%, 60% to 99%, 60% to 98%, 60% to 95%, 65% to 99.999999 %, 65% to 99.99999%, 65% to 99.9999%, 65% to 99.999%, 65% to 100%, 65% to 99.99%, 65% to 99.99%, 65% to 99%, 65% to 99%, 65% to 98%, 65% to 95%, 70% to 100%, 70% to 99.9 ... 0% to 99.999%, 70% to 99.99%, 70% to 99.9%, 70% to 99%, 70% to 98%, 70% to 95%, 75% to 100%, 75% to 99.99%, 75% to 99.99%, 75% to 99.99999%, 75% to 99.99999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, The invention further provides that the amount of the composition may be used to inhibit the growth (reduced growth) of Staphylococcus aureus by 75% to 98%, 75% to 95%, 80% to 99.99999%, 80% to 99.99999%, 80% to 99.9999%, 80% to 99.9999%, 80% to 100%, 80% to 99.99%, 80% to 99.99%, 80% to 99%, 80% to 98%, or 80% to 95%. In terms of lower limits, the improved AM / AV fibers / fabrics can inhibit the growth of Staphylococcus aureus by greater than 60%, for example, greater than 65%, greater than 70%, greater than 75%, greater than 80%, greater than 85%, greater than 90%, greater than 95%, greater than 98%, greater than 99%, greater than 99.9%, greater than 99.99%, greater than 99.999%, greater than 99.9999%, greater than 99.99999%, or greater than 99.999999%.

[0058] Klebsiella pneumoniae efficacy can also be determined using the above test. In some embodiments, the product formed from the polymer composition inhibits the growth of Klebsiella pneumoniae (reduced growth) as measured by the above test. Escherichia coli can be determined using ASTM E3160 (2018). The ranges and limits for Staphylococcus aureus also apply to Escherichia coli and / or Klebsiella pneumoniae and / or SARS-CoV-2.

[0059] Effectiveness can be characterized by log reduction. For E. coli log reduction, the improved AM / AV fibers / fabrics can be measured by ASTM 3160 (2018) and can exhibit an E. coli log reduction of greater than 1.5, e.g., greater than 2.0, greater than 2.15, greater than 2.5, greater than 2.7, greater than 3.0, greater than 3.3, greater than 4.0, greater than 4.1, greater than 5.0, or greater than 6.0.

[0060] For S. aureus log reduction, the improved AM / AV fibers / fabrics may be measured by ISO 20743:2013 and may exhibit a microbial log reduction of greater than 1.5, e.g., greater than 2.0, greater than 2.5, greater than 2.7, greater than 3.0, greater than 4.0, greater than 5.0, or greater than 6.0.

[0061] For Klebsiella pneumoniae log reduction, the improved AM / AV fibers / fabrics may be measured by ISO 20743:2013 and may exhibit a microbial log reduction of greater than 1.5, e.g., greater than 2.0, greater than 2.5, greater than 2.6, greater than 3.0, greater than 4.0, greater than 5.0, or greater than 6.0.

[0062] For SARS-CoV-2 log reduction, the improved AM / AV fibers / fabrics can be measured by ISO 18184:2019 and can exhibit a viral log reduction of greater than 1.5, e.g., greater than 1.7, greater than 2.0, greater than 2.5, greater than 2.6, greater than 3.0, greater than 4.0, greater than 5.0, or greater than 6.0.

[0063] AM / AV properties may include any antiviral effects. In some embodiments, for example, the antiviral properties of the improved AM / AV fibers / fabrics include limiting, reducing or inhibiting viral infection. In some embodiments, the antiviral properties of the AM / AV materials include limiting, reducing or inhibiting viral pathogenic mechanisms. In some cases, the polymer composition can limit, reduce or inhibit viral infection and pathogenic mechanisms.

[0064] The viruses affected by the antiviral properties of the improved AM / AV fibers / fabrics are not particularly limited. In some embodiments, for example, the virus is an adenovirus, herpes virus, Ebola virus, poxvirus, rhinovirus, coxsackie virus, arteritis virus, enterovirus, measles virus, coronavirus, influenza A virus, avian influenza virus, swine influenza virus, or equine influenza virus. In some embodiments, the antiviral properties include limiting, reducing, or inhibiting the infection or pathogenicity of one of the viruses, such as from the above list. In some embodiments, the antiviral properties include limiting, reducing, or inhibiting the infection or pathogenicity of multiple viruses, such as a combination of two or more viruses from the above list.

[0065] In some cases, the virus is a coronavirus, such as severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV), or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (e.g., the coronavirus that causes COVID-19). In some cases, the virus is structurally related to a coronavirus.

[0066] In some cases, the virus is an influenza virus, such as influenza A, influenza B, influenza C, or influenza D, or a structurally related virus. In some cases, the virus is identified as an influenza A subtype, such as H1N1, H1N2, H2N2, H2N3, H3N1, H3N2, H3N8, H5N1, H5N2, H5N3, H5N6, H5N8, H5N9, H6N1, H7N1, H7N4, H7N7, H7N9, H9N2, or H10N7.

[0067] In some cases, the virus is a bacteriophage, such as a linear or circular single-stranded DNA virus (e.g., phi X 174 (sometimes referred to as ΦX174)), a linear or circular double-stranded DNA, a linear or circular single-stranded RNA, or a linear or circular double-stranded RNA. In some cases, the antiviral properties of the polymer composition can be measured by using a bacteriophage, such as a phi X 174 test.

[0068] In some cases, the virus is an Ebola virus, such as Bundibugyo ebolavirus (BDBV), Reston ebolavirus (RESTV), Sudan ebolavirus (SUDV), Tai Forest ebolavirus ( In some cases, the virus is structurally related to the Ebola virus.

[0069] Antiviral activity can be measured by various conventional methods. For example, ISO 18184:2019 can be used to evaluate antiviral activity. In one embodiment, the improved AM / AV fiber / fabric has a content of 60% to 100%, such as 60% to 99.99999%, 60% to 99.99999%, 60% to 99.99999%, 60% to 99.9999%, 60% to 99.999%, 60% to 99.99%, 60% to 99.9%, 60% to 99%, 60% to 98%, 60% to 95%, 65% to 99.99999 9%, 65% to 99.99999%, 65% to 99.9999%, 65% to 99.999%, 65% to 100%, 65% to 99.99%, 65% to 99.99%, 65% to 99%, 65% to 99%, 65% to 98%, 65% to 95%, 70% to 100%, 70% to 99.99999%, 70% to 99.99999%, 70% to 99.99999% , 70% to 99.999%, 70% to 99.99%, 70% to 99.9%, 70% to 99%, 70% to 98%, 70% to 95%, 75% to 100%, 75% to 99.99%, 75% to 99.99%, 75% to 99.99999%, 75% to 99.99999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to An amount of 99%, 75% to 98%, 75% to 95%, 80% to 99.999999%, 80% to 99.99999%, 80% to 99.99999%, 80% to 99.9999%, 80% to 100%, 80% to 99.99%, 80% to 99.99%, 80% to 99%, 80% to 98%, or 80% to 95% inhibits the pathogenic mechanisms (e.g., growth) of the virus. In terms of lower limits, the improved AM / AV fibers / fabrics can inhibit greater than 60% of viral pathogenic mechanisms, for example, greater than 65%, greater than 70%, greater than 75%, greater than 80%, greater than 85%, greater than 90%, greater than 95%, greater than 98%, greater than 99%, greater than 99.9%, greater than 99.99%, greater than 99.999%, greater than 99.9999%, greater than 99.99999%, or greater than 99.999999%.

[0070] In addition, the use of the polymer compositions disclosed herein provides biocompatibility advantages. For example, the overall softness and compositional characteristics of the above-mentioned fabrics achieve unexpected reductions in irritation and sensitization. Beneficially, the disclosed fibers and fabrics do not exhibit biocompatibility issues associated with conventional fabrics, such as fabrics using metals with toxicity issues, such as silver. For example, as tested according to ISO 10993-10 and 10993-12, the AM / AV polymer composition exhibits acceptable results in terms of irritation and sensitization.

[0071] AM / AV polymer composition

[0072] As described above, the AM / AV materials of the present disclosure may include polymer compositions that beneficially exhibit antimicrobial and / or antiviral properties. For example, a fabric sheet may be made of and / or may include an antimicrobial / antiviral polymer composition as described herein.

[0073] AM / AV polymer compositions suitable for use in the AM / AV materials described herein generally comprise a polymer and one or more AM / AV compounds, such as a metal (e.g., a metal compound). In some embodiments, the polymer composition comprises a polymer, zinc (provided to the composition via a zinc compound) and / or phosphorus (provided to the composition via a phosphorus compound). In some embodiments, the polymer composition comprises a polymer, copper (provided to the composition via a copper compound) and phosphorus (provided to the composition via a phosphorus compound).

[0074] Exemplary polymer compositions are disclosed in U.S. Patent Application No. 17 / 192,491, filed on March 4, 2021, and U.S. Patent Application No. 17 / 192,533, filed on March 4, 2021, both of which are incorporated herein by reference.

[0075] polymer

[0076] The polymer composition comprises a polymer, which in some embodiments is a polymer suitable for producing fibers and fabrics. In one embodiment, the polymer composition comprises a polymer of 50 wt % to 100 wt %, for example 50 wt % to 99.99 wt %, 50 wt % to 99.9 wt %, 50 wt % to 99 wt %, 55 wt % to 100 wt %, 55 wt % to 99.99 wt %, 55 wt % to 99.9 wt %, 55 wt % to 99 wt %, 60 wt % to 100 wt %, 60 wt % to 99.99 wt %, 60 wt % to 99.9 wt %, 60 wt % to 99 wt %., 65 wt % to 100 wt %, 65 wt % to 99.99 wt %, 65 wt % to 99.9 wt %, or a polymer of 65 wt % to 99 wt %. In terms of upper limits, the polymer composition may include less than 100 wt % of polymer, such as less than 99.99 wt %, less than 99.9 wt % or less than 99 wt %. In terms of lower limits, the polymer composition may include greater than 50 wt % of polymer, such as greater than 55 wt %, greater than 60 wt % or greater than 65 wt %.

[0077] The polymer of the polymer composition can be very different. The polymer may include, but is not limited to, thermoplastic polymers, polyesters, nylons, rayon, polyamide 6, polyamide 6,6, polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyethylene terephthalate (PETG), co-PET, polybutylene terephthalate (PBT), polylactic acid (PLA) and polytrimethylene terephthalate (PTT). In some embodiments, the polymer composition may include PET due to its strength, durability during washing, durable pressing ability and ability to blend with other fibers. In some embodiments, the polymer may be PA6,6. In some cases, nylon is known to be a stronger fiber than PET and exhibits non-drip burning characteristics, which is, for example, beneficial in military or automotive textile applications and more hydrophilic than PET. The polymer used in the present disclosure may be polyamide, polyetheramide, polyetherester or polyetherurethane or a mixture thereof.

[0078] In some cases, the polymer composition may include polyethylene. Suitable examples of polyethylene include linear low density polyethylene (LLDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), and ultra high molecular weight polyethylene (UHMWPE).

[0079] In some cases, the polymer composition may include polycarbonate (PC). For example, the polymer composition may include blends of polycarbonate with other polymers, such as blends of polycarbonate and acrylonitrile butadiene styrene (PC-ABS), blends of polycarbonate and polyvinyl toluene (PC-PVT), blends of polycarbonate and polybutylene terephthalate (PC-PBT), blends of polycarbonate and polyethylene terephthalate (PC-PET), or combinations thereof.

[0080] In some cases, the polymer composition may include polyamide. Common polyamides include nylon and aromatic polyamide. For example, the polyamide may include PA-4T / 4I; PA-4T / 6I; PA-5T / 5I; PA-6; PA6,6; PA6,6 / 6; PA6,6 / 6T; PA-6T / 6I; PA-6T / 6I / 6; PA-6T / 6; PA-6T / 6I / 66; PA-6T / MPMDT (wherein MPMDT is a polyamide based on a mixture of hexamethylenediamine and 2-methylpentamethylenediamine as a diamine component and terephthalic acid as a diacid component); PA-6T / 66; PA-6T / 61 0; PA-10T / 612; PA-10T / 106; PA-6T / 612; PA-6T / 10T; PA-6T / 10I; PA-9T; PA-10T; PA-12T; PA-10T / 10I; PA-10T / 12; PA-10T / 11; PA-6T / 9T; PA-6T / 12T; PA-6T / 10T / 6I; PA-6T / 6I / 6; PA-6T / 61 / 12; and copolymers, blends, mixtures and / or other combinations thereof. Additional suitable polyamides, additives and other components are disclosed in U.S. Patent Application No. 16 / 003,528. In some cases, the polymer comprises PA6 or PA 6,6 or a combination thereof.

[0081] In some embodiments, the polymer composition comprises a thermoplastic polymer, polyester, nylon, rayon, polyamide, polyamide, polyolefin, polyolefin terephthalate, polyolefin terephthalate glycol, co-PET, or polylactic acid, or a combination thereof.

[0082] In other embodiments, the polymer composition is blended with absorbent fibers, such as rayon, lyocell and / or natural fibers, such as cotton or hemp. For example, the polymer composition can be PA-66 blended with rayon or lyocell.

[0083] The polymer composition may comprise a combination of polyamides in some embodiments. By combining various polyamides, the final composition is able to combine the desirable properties of each component polyamide, such as mechanical properties. For example, in some embodiments, the polyamide comprises a combination of PA-6, PA6,6, and PA6,6 / 6T. In these embodiments, the polyamide may comprise 1 wt % to 99 wt % PA-6, 30 wt % to 99 wt % PA6,6, and 1 wt % to 99 wt % PA6,6 / 6T. In some embodiments, the polyamide comprises one or more of PA-6, PA6,6, and PA6,6 / 6T. In some aspects, the polymer composition comprises 6 wt % PA-6 and 94 wt % PA6,6. In some aspects, the polymer composition comprises a copolymer or blend of any polyamide mentioned herein.

[0084] The polymer composition may also include the polyamide made by the ring-opening polymerization or polycondensation of lactam, including copolymerization and / or co-condensation. Not limited by theory, these polyamides may include those made by propiolactam, butyrolactam, valerolactam and caprolactam. For example, in some embodiments, the polyamide is a polymer derived from the polymerization of caprolactam. In these embodiments, the polymer includes at least 10 % by weight caprolactam, for example at least 15 % by weight, at least 20 % by weight, at least 25 % by weight, at least 30 % by weight, at least 35 % by weight, at least 40 % by weight, at least 45 % by weight, at least 50 % by weight, at least 55 % by weight or at least 60 % by weight. In some embodiments, the polymer includes the caprolactam of 10 % by weight to 60 % by weight, for example 15 % by weight to 55 % by weight, 20 % by weight to 50 % by weight, 25 % by weight to 45 % by weight or 30 % by weight to 40 % by weight. In some embodiments, the polymer comprises less than 60 wt% caprolactam, such as less than 55 wt%, less than 50 wt%, less than 45 wt%, less than 40 wt%, less than 35 wt%, less than 30 wt%, less than 25 wt%, less than 20 wt%, or less than 15 wt%. In addition, the polymer composition may comprise a polyamide made by copolymerization of lactam and nylon, such as the copolymerization product of caprolactam and PA6,6.

[0085] In some aspects, the polymer can be formed by conventional polymerization of a polymer composition, wherein an aqueous solution of at least one diamine-carboxylate salt is heated to remove water and achieve polymerization to form an antiviral nylon. This aqueous solution is preferably a mixture comprising at least one polyamide-forming salt and a specific amount of a zinc compound, a copper compound, and / or a phosphorus compound as described herein to produce a polymer composition. Conventional polyamide salts are formed by the reaction of a diamine with a dicarboxylic acid, and the resulting salt provides a monomer. In some embodiments, a preferred polyamide-forming salt is hexamethylenediamine adipate (nylon 6,6 salt) formed by the reaction of equimolar amounts of hexamethylenediamine and adipic acid.

[0086] Different polymers can be used to form different fibers, thereby forming the overall base fiber. The base fiber can include AM / AV base fibers and companion fibers. The AM / AV base fiber can be made from an AM / AV composition. The companion fiber can be made from different polymer compositions with or without AM / AV compounds.

[0087] In some cases, the polymer comprises a natural polymer or a natural fiber, such as cotton or cellulose / wood pulp.

[0088] In some embodiments, the polymer does not include natural polymers or natural fibers. For example, the polymer may contain less than 10% by weight of natural polymers or natural fibers, such as less than 5% by weight, less than 3% by weight, less than 1% by weight, less than 0.5% by weight, or less than 0.1% by weight. In some cases, the polymer is almost or completely free of cotton.

[0089] In some embodiments, the polymer comprises a combination of natural and synthetic polymers. For example, the polymer may comprise polyamide and / or cotton and / or cellulose. In some cases, the polymer comprises polyamide and cotton.

[0090] AM / AV (metal) compounds

[0091] As described above, the polymer composition may include one or more AM / AV compounds, which may be in the form of metal compounds. In some embodiments, the polymer composition includes zinc, such as in a zinc compound, optionally phosphorus, such as in a phosphorus compound, optionally copper, such as in a copper compound, optionally silver, such as in a silver compound, or a combination thereof. As used herein, a metal compound refers to a compound having at least one metal molecule or ion, for example, a "zinc compound" refers to a compound having at least one zinc molecule or ion.

[0092] Some conventional polymer compositions, fibers and fabrics utilize AM / AV compounds to inhibit viruses and other pathogens. For example, some fabrics may include antimicrobial additives, such as silver, applied as a coating or as a film on the outer surface. However, it has been found that these treatments or coatings often bring many problems. For example, the coated additives may leach from the fiber / fabric during dyeing or washing, which adversely affects the antimicrobial and / or antiviral properties. With regard to conventional products, certain coatings, such as silver, may cause health and / or even environmental problems when used continuously. Compared with conventional formulations, the polymer compositions disclosed herein include a unique combination of AM / AV compounds (e.g., metal compounds), rather than simply applying the AM / AV compounds on the surface. In other words, the polymer composition can embed a certain amount of metal compounds in the polymer matrix so that the polymer composition maintains the AM / AV properties during and after dyeing and / or washing.

[0093] In one embodiment, the AM / AV compound may be added as a masterbatch. The masterbatch may include a polyamide such as nylon 6 or nylon 6,6. Other masterbatch compositions are contemplated.

[0094] The polymer composition may include a metal compound, such as a metal or a metal compound dispersed in the polymer composition. In one embodiment, the polymer composition includes 5wppm to 20,000wppm, such as 5wppm to 17,500wppm, 5wppm to 17,000wppm, 5wppm to 16,500wppm, 5wppm to 16,000wppm, 5wppm to 15,500wppm, 5wppm to 15,000wppm, 5wppm to 12,500wppm, 5wppm to 10,000wppm, 5wppm to 5000wppm, 5wppm to 4000wppm, such as 5wppm to 3000wppm, 5wppm to 2000wppm, 5wppm to 1000wppm, 5wppm to 500wppm, 10wppm to 20,000wppm, 10wppm to 17,500wppm, 10wppm to 17,000wppm, 10wppm to 16,500wppm, 10wppm to 16,000wppm, 10wppm to 15,500wppm, 10wppm to 15,000wppm, 10wppm to 12,500wppm, 10wppm to 10,000wppm, 10wppm to 5000wppm, 10wppm to 4000wppm, 10wppm to 3000wppm ppm, 10wppm to 2000wppm, 10wppm to 1000wppm, 10wppm to 500wppm, 50wppm to 20,000wppm, 50wppm to 17,500wppm, 50wppm to 17,000wppm, 50wppm to 16,500wppm, 50wppm to 16,000wppm, 50wppm to 15,500wppm, 50wppm to 15,000wppm, 50wppm to 12,500wppm, 50wppm to 10,000wppm, 50wppm to 5000wppm, 50wppm to wppm, 100wppm to 15,500wppm, 100wppm to 15,000wppm, 100wppm to 12,500wppm, 100wppm to 10,000wppm, 100wppm to 20,000wppm, 100wppm to 17,500wppm, 100wppm to 17,000wppm, 100wppm to 16,500wppm, 100wppm to 16,000wppm, 100wppm to 15,500wppm, 100wppm to 15,000wppm, 100wppm to 12,500wppm, 100wppm to 10,100wppm to 5000wppm, 100wppm to 4000wppm, 100wppm to 3000wppm, 100wppm to 2000wppm, 100wppm to 1000wppm, 100wppm to 500wppm, 200wppm to 20,000wppm, 200wppm to 17,500wppm, 200wppm to 17,000wppm, 200wppm to 16,500wppm, 200wppm to 16 ,000wppm, 200wppm to 15,500wppm, 200wppm to 15,000wppm, 200wppm to 12,500wppm, 200wppm to 10,000wppm, 200wppm to 5000wppm, 200wppm to 4000wppm, 200wppm to 3000wppm, 200wppm to 2000wppm, 200wppm to 1000wppm, or 200wppm to 500wppm. ,

[0095] In terms of lower limits, the polymer composition may include greater than 5wppm of metal compounds, such as greater than 10wppm, greater than 50wppm, greater than 100wppm, greater than 200wppm or greater than 300wppm. In terms of upper limits, the polymer composition may include less than 20,000wppm of metal compounds, such as less than 17,500wppm, less than 17,000wppm, less than 16,500wppm, less than 16,000wppm, less than 15,500wppm, less than 15,000wppm, less than 12,500wppm, less than 10,000wppm, less than 5000wppm, less than 4000wppm, less than 3000wppm, less than 2000wppm, less than 1000wppm or less than 500wppm. As described above, the metal compound is preferably embedded in the polymer formed by the polymer composition.

[0096] As described above, the polymer composition includes zinc in a zinc compound and phosphorus in a phosphorus compound, preferably in a specific amount in the polymer composition to provide the above-mentioned structural benefits and antiviral benefits. "Zinc compound" as used herein refers to a compound having at least one zinc molecule or ion (copper compounds are also the same). "Phosphorus compound" as used herein refers to a compound having at least one phosphorus molecule or ion. The zinc content can be represented by zinc or zinc ions (the same applies to copper). Ranges and limits can be used for zinc content and zinc ion content, as well as for other metal contents, such as copper content. Calculations based on the zinc ion content of zinc or zinc compounds can be performed by chemical technicians, and such calculations and adjustments are taken into account.

[0097] The polymer composition may include zinc, for example, in a zinc compound or as a zinc ion, for example, zinc or a zinc compound dispersed in the polymer composition. In one embodiment, the polymer composition includes 5wppm to 20,000wppm, for example, 5wppm to 17,500wppm, 5wppm to 17,000wppm, 5wppm to 16,500wppm, 5wppm to 16,000wppm, 5wppm to 15,500wppm, 5wppm to 15,000wppm, 5wppm to 12,500wppm, 5wppm to 10,000wppm, 5wppm to 5000wppm, 5wppm to 4000wppm, for example, 5wppm to 3000wppm, 5wppm to 2000wppm, 5wppm to 1000wppm, 5wppm to 500wppm, 10wppm to 20,000wppm, 10wppm to 17,500wppm, 10wppm to 17,000wppm, 10wppm to 16,500wppm, 10wppm to 16,000wppm, 10wppm to 15,500wppm, 10wppm to 15,000wppm, 10wppm to 12,500wppm, 10wppm to 10,000wppm, 10wppm to 5000wppm, 10wppm to 4000wppm, 10wppm to 3000wppm ppm, 10wppm to 2000wppm, 10wppm to 1000wppm, 10wppm to 500wppm, 50wppm to 20,000wppm, 50wppm to 17,500wppm, 50wppm to 17,000wppm, 50wppm to 16,500wppm, 50wppm to 16,000wppm, 50wppm to 15,500wppm, 50wppm to 15,000wppm, 50wppm to 12,500wppm, 50wppm to 10,000wppm, 50wppm to 5000wppm, 50wppm to wppm, 100wppm to 15,500wppm, 100wppm to 15,000wppm, 100wppm to 12,500wppm, 100wppm to 10,000wppm, 100wppm to 20,000wppm, 100wppm to 17,500wppm, 100wppm to 17,000wppm, 100wppm to 16,500wppm, 100wppm to 16,000wppm, 100wppm to 15,500wppm, 100wppm to 15,000wppm, 100wppm to 12,500wppm, 100wppm to 10,100wppm to 5000wppm, 100wppm to 4000wppm, 100wppm to 3000wppm, 100wppm to 2000wppm, 100wppm to 1000wppm, 100wppm to 500wppm, 200wppm to 20,000wppm, 200wppm to 17,500wppm, 200wppm to 17,000wppm, 200wppm to 16,500wppm, 200wppm to 16,000wppm, 200wppm to 15,500wppm 0wppm, 200wppm to 15,000wppm, 200wppm to 12,500wppm, 200wppm to 10,000wppm, 200wppm to 5000wppm, 200wppm to 4000wppm, 5000wppm to 20000wppm, 200wppm to 3000wppm, 200wppm to 2000wppm, 200wppm to 1000wppm, 200wppm to 500wppm, 10wppm to 900wppm, 200wppm to 900wppm, from From 425wppm to 600wppm, from 425wppm to 525wppm, from 350wppm to 600wppm, from 375wppm to 600wppm, from 375wppm to 525wppm, from 480wppm to 600wppm, from 480wppm to 525wppm, from 600wppm to 750wppm, or from 600wppm to 700wppm.

[0098] In terms of lower limits, the polymer composition can contain greater than 5 wppm zinc, e.g., greater than 10 wppm, greater than 50 wppm, greater than 100 wppm, greater than 200 wppm, greater than 300 wppm, greater than 350 wppm, greater than 375 wppm, greater than 400 wppm, greater than 425 wppm, greater than 480 wppm, greater than 500 wppm, or greater than 600 wppm.

[0099] In terms of upper limits, the polymer composition can comprise less than 20,000 wppm zinc, e.g., less than 17,500 wppm, less than 17,000 wppm, less than 16,500 wppm, less than 16,000 wppm, less than 15,500 wppm, less than 15,000 wppm, less than 12,500 wppm, less than 10,000 wppm, less than 5000 wppm, less than 4000 wppm, less than 3000 wppm, less than 2000 wppm, less than 1000 wppm, less than 500 wppm, less than 400 wppm, less than 330 wppm, less than 300. In some aspects, the zinc compound is embedded in a polymer formed from the polymer composition.

[0100] The ranges and limits apply to both elemental or ionic zinc and zinc compounds. The same is true for other ranges and limits disclosed herein for other metals, such as copper. For example, a range may relate to the amount of zinc ions dispersed in a polymer.

[0101] The zinc of the polymer composition is present in or provided by the zinc compound, and the zinc compound can be very different. The zinc compound can include zinc oxide, zinc ammonium adipate, zinc acetate, zinc ammonium carbonate, zinc stearate, zinc phenyl phosphinate (zincphenyl phosphinic acid) or zinc pyrithione or its combination. In some embodiments, the zinc compound includes zinc oxide, zinc ammonium adipate, zinc acetate or zinc pyrithione or its combination. In some embodiments, the zinc compound includes zinc oxide, zinc stearate or zinc ammonium adipate or its combination. In some aspects, zinc is provided in the form of zinc oxide. In some aspects, zinc is not provided by zinc phenyl phosphinate (zinc phenyl phosphinate) and / or zinc phenyl phosphinate.

[0102] The present inventors have also found that the polymer composition surprisingly benefits from the use of specific zinc compounds. In particular, zinc ions (e.g., Zn 2+The use of zinc compounds of the invention can improve the antiviral properties of the polymer composition. It is inferred that ionic zinc interferes with the replication cycle of the virus. For example, ionic zinc may interfere with (e.g., inhibit) viral protease or polymerase activity. Further discussion of the effects of ionic zinc on viral activity can be found in Velthuis et al., Zn Inhibits Coronavirus and Arterivirus RNA Polymerase Activity In Vitro and Zinc Ionophores Block the Replication of These Viruses in Cell Culture, PLoS Pathogens (November 2010), which is incorporated herein by reference.

[0103] The amount of zinc compound present in the polymer composition may be discussed in terms of ionic zinc content. In one embodiment, the polymer composition comprises from 1 wppm to 30,000 wppm, e.g., from 1 wppm to 25,000 wppm, from 1 wppm to 20,000 wppm, from 1 wppm to 15,000 wppm, from 1 wppm to 10,000 wppm, from 1 wppm to 5,000 wppm, from 1 wppm to 2,500 wppm, from 50 wppm to 30,000 wppm, from 50 wppm to 25,000 wppm, 00wppm, 50wppm to 20,000wppm, 50wppm to 15,000wppm, 50wppm to 10,000wppm, 50wppm to 5,000wppm, 50wppm to 2,500wppm, 100wppm to 30,000wppm, 100wppm to 25,000wppm, 100wppm to 20,000wppm, 100wppm to 15,000wppm wppm, 100wppm to 10,000wppm, 100wppm to 5,000wppm, 100wppm to 2,500wppm, 150wppm to 30,000wppm, 150wppm to 25,000wppm, 150wppm to 20,000wppm, 150wppm to 15,000wppm, 150wppm to 10,000wppm, 150wppm to 5,0 00 wppm, 150 wppm to 2,500 wppm, 250 wppm to 30,000 wppm, 250 wppm to 25,000 wppm, 250 wppm to 20,000 wppm, 250 wppm to 15,000 wppm, 250 wppm to 10,000 wppm, 250 wppm to 5,000 wppm, or 250 wppm to 2,500 wppm.2+ In some cases, the ranges and limits noted above for zinc may also apply to the ionic zinc content.

[0104] The zinc can be embedded in the polymer matrix. For example, the fiber can include embedded zinc, such as ionic zinc (Zn 2+ ) of a polyamide polymer matrix.

[0105] In some cases, the use of zinc provides processing and or end-use benefits. Other antiviral agents, such as copper or silver, can be used, but these generally include adverse effects (e.g., relative viscosity, toxicity, and health or environmental risks to the polymer composition). In some cases, zinc has no adverse effect on the relative viscosity of the polymer composition. In addition, unlike other antiviral agents, such as silver, zinc does not have toxicity issues (and may actually provide health advantages, such as immune system support). In addition, as described herein, the use of zinc can reduce or eliminate leaching into other media and / or the environment. This prevents the risks associated with introducing zinc into the environment and enables the polyamide composition to be reused-compared with conventional (e.g., silver-containing) compositions, zinc provides a surprising "green" advantage.

[0106] As noted above, the polymer composition, in some embodiments, includes copper (provided via a copper compound). As used herein, "copper compound" refers to a compound having at least one copper molecule or ion.

[0107] In some cases, the copper compound can improve, for example, enhance the antiviral properties of the polymer composition. In some cases, the copper compound may affect other properties of the polymer composition, such as antimicrobial activity or physical properties.

[0108] The polymer composition may include copper (e.g., in a copper compound), such as copper or a copper compound dispersed in the polymer composition. In one embodiment, the polymer composition includes 5wppm to 20,000wppm, such as 5wppm to 17,500wppm, 5wppm to 17,000wppm, 5wppm to 16,500wppm, 5wppm to 16,000wppm, 5wppm to 15,500wppm, 5wppm to 15,000wppm, 5wppm to 12,500wppm, 5wppm to 10,000wppm, 5wppm to 5000wppm, 5wppm to 4000wppm, such as 5wppm to 3000wppm, 5wppm to 2000wppm, 5wppm to 1000wppm, 5wppm to 500wppm, 5wppm to 100wppm, 5wppm to 50wppm, 5wppm to 35wppm, 10wppm to 20,000wppm, 10wppm to 17,500wppm, 10wppm to 17,000wppm, 10wppm to 16,500wppm, 10wppm to 16,000wppm, 10wppm to 15,500wppm, 10wppm to 15,000wppm, 10wppm to 12,500wppm, 10wppm to 10,000wppm, 10wppm to 15,500wppm wppm, 50wppm to 15,500wppm, 50wppm to 15,000wppm, 50wppm to 12,500wppm, 50wppm to 15,000wppm, 50wppm to 12,500wppm, 50wppm to 20,000wppm, 50wppm to 17,500wppm, 50wppm to 17,000wppm, 50wppm to 16,500wppm, 50wppm to 16,000wppm, 50wppm to 15,500wppm, 50wppm to 15,000wppm, 50wppm to 12,500wppm, 50wppm to 15,000wppm, 50wppm to 12,500wppm, 50wppm to 20,000wppm, 50wppm to 17,500wppm, 50wppm to 17,000wppm, wppm to 10,000wppm, 50wppm to 5000wppm, 50wppm to 4000wppm, 50wppm to 3000wppm, 50wppm to 2000wppm, 50wppm to 1000wppm, 50wppm to 500wppm, 100wppm to 20,000wppm, 100wppm to 17,500wppm, 100wppm to 17,000wppm, 100wppm to 16,500wppm, 100wppm to 16,000wppm, 100wppm to 15,500wppm, 100wppm to 15,100wppm to 12,500wppm, 100wppm to 10,000wppm, 100wppm to 5000wppm, 100wppm to 4000wppm, 100wppm to 3000wppm, 100wppm to 2000wppm, 100wppm to 1000wppm, 100wppm to 500wppm, 200wppm to 20,000wppm, 200wppm to 17,500wppm, 200wppm to 17,000wppm, 200wppm to 16,500wppm, 200wppm to 20,000wppm wppm, 200 wppm to 3000 wppm, 200 wppm to 2000 wppm, 200 wppm to 1000 wppm, or 200 wppm to 500 wppm. ,

[0109] In terms of lower limits, the polymer composition may contain greater than 5 wppm copper, such as greater than 10 wppm, greater than 50 wppm, greater than 100 wppm, greater than 109 wppm, greater than 200 wppm, or greater than 300 wppm. In terms of upper limits, the polymer composition may contain less than 20,000 wppm copper, such as less than 17,500 wppm, less than 17,000 wppm, less than 16,500 wppm, less than 16,000 wppm, less than 15,500 wppm, less than 15,000 wppm, less than 12,500 wppm, less than 10,000 wppm, less than 5000 wppm, less than 4000 wppm, less than 3000 wppm, less than 2000 wppm, less than 1000 wppm, less than 500 wppm, less than 350 wppm, less than 100 wppm, less than 50 wppm, less than 35 wppm. In some aspects, the copper compound is embedded in a polymer formed from the polymer composition.

[0110] The composition of the copper compound is not particularly limited. Suitable copper compounds include copper iodide, copper bromide, copper chloride, copper fluoride, copper oxide, copper stearate, cuprammonium adipate, copper acetate or copper pyrithione or a combination thereof. The copper compound may include copper oxide, cuprammonium adipate, cupric acetate, cuprammonium carbonate, copper stearate, copper phenylphosphinate or copper pyrithione or a combination thereof. In some embodiments, the copper compound includes copper oxide, cuprammonium adipate, cupric acetate or copper pyrithione or a combination thereof. In some embodiments, the copper compound includes copper oxide, cuprammonium adipate, cupric acetate or copper pyrithione or a combination thereof. In some aspects, copper is provided in the form of copper oxide. In some aspects, copper is not provided by copper phenylphosphinate and / or copper phenylphosphinate.

[0111] In some cases, the polymer composition includes silver (optionally provided via a silver compound). As used herein, "silver compound" refers to a compound having at least one silver molecule or ion. The silver may be in ionic form. The ranges and limits for silver may be similar to those for copper (discussed above).

[0112] In one embodiment, the molar ratio of copper to zinc is greater than 0.01:1, e.g., greater than 0.05:1, greater than 0.1:1, greater than 0.15:1, greater than 0.25:1, greater than 0.5:1, or greater than 0.75:1. In terms of ranges, the molar ratio of copper to zinc in the polymer composition may be from 0.01:1 to 15:1, e.g., from 0.05:1 to 10:1, from 0.1:1 to 9:1, from 0.15:1 to 8:1, from 0.25:1 to 7:1, from 0.5:1 to 6:1, from 0.75:1 to 5:1, from 0.5:1 to 4:1, or from 0.5:1 to 3:1. In terms of upper limits, the molar ratio of zinc to copper in the polymer composition may be less than 15:1, e.g., less than 10:1, less than 9:1, less than 8:1, less than 7:1, less than 6:1, less than 5:1, less than 4:1, or less than 3:1. In some cases, the copper is incorporated with the zinc in a polymer matrix.

[0113] In some embodiments, the use of cuprous ammonium adipate has been found to be particularly effective for activating copper ions into a polymer matrix. Similarly, the use of silver ammonium adipate has been found to be particularly effective for activating silver ions into a polymer matrix. Dissolving a copper (I) or copper (II) compound in ammonium adipate has been found to be particularly effective for generating copper (I) or copper (II) ions. The same applies to dissolving an Ag (I) or Ag (III) compound in ammonium adipate to generate Ag. 1+ or Ag 3+ ion.

[0114] The polymer composition may include silver (e.g., in a silver compound), such as silver or a silver compound dispersed in the polymer composition. In one embodiment, the polymer composition includes 5wppm to 20,000wppm, such as 5wppm to 17,500wppm, 5wppm to 17,000wppm, 5wppm to 16,500wppm, 5wppm to 16,000wppm, 5wppm to 15,500wppm, 5wppm to 15,000wppm, 5wppm to 12,500wppm, 5wppm to 10,000wppm, 5wppm to 5000wppm, 5wppm to 4000wppm, such as 5wppm to 3000wppm, 5wppm to 2000wppm, 5wppm to 1000wppm, 5wppm to 500wppm, 10wppm to 20,000wppm, 10wppm to 17,500wppm, 10wppm to 17,000wppm, 10wppm to 16,500wppm, 10wppm to 16,000wppm, 10wppm to 15,500wppm, 10wppm to 15,000wppm, 10wppm to 12,500wppm, 10wppm to 10,000wppm, 10wppm to 5000wppm, 10wppm to 4000wppm, 10wppm to 3000wppm ppm, 10wppm to 2000wppm, 10wppm to 1000wppm, 10wppm to 500wppm, 50wppm to 20,000wppm, 50wppm to 17,500wppm, 50wppm to 17,000wppm, 50wppm to 16,500wppm, 50wppm to 16,000wppm, 50wppm to 15,500wppm, 50wppm to 15,000wppm, 50wppm to 12,500wppm, 50wppm to 10,000wppm, 50wppm to 5000wppm, 50wppm to wppm, 100wppm to 15,500wppm, 100wppm to 15,000wppm, 100wppm to 12,500wppm, 100wppm to 10,000wppm, 100wppm to 20,000wppm, 100wppm to 17,500wppm, 100wppm to 17,000wppm, 100wppm to 16,500wppm, 100wppm to 16,000wppm, 100wppm to 15,500wppm, 100wppm to 15,000wppm, 100wppm to 12,500wppm, 100wppm to 10,100wppm to 5000wppm, 100wppm to 4000wppm, 100wppm to 3000wppm, 100wppm to 2000wppm, 100wppm to 1000wppm, 100wppm to 500wppm, 200wppm to 20,000wppm, 200wppm to 17,500wppm, 200wppm to 17,000wppm, 200wppm to 16,500wppm, 200wppm to 16,000 wppm, 200 wppm to 15,500 wppm, 200 wppm to 15,000 wppm, 200 wppm to 12,500 wppm, 200 wppm to 10,000 wppm, 200 wppm to 5000 wppm, 200 wppm to 4000 wppm, 200 wppm to 3000 wppm, 200 wppm to 2000 wppm, 200 wppm to 1000 wppm, or 200 wppm to 500 wppm. ,

[0115] In terms of lower limits, the polymer composition may include greater than 5wppm of silver, such as greater than 10wppm, greater than 50wppm, greater than 100wppm, greater than 200wppm, or greater than 300wppm. In terms of upper limits, the polymer composition may include less than 20,000wppm of silver, such as less than 17,500wppm, less than 17,000wppm, less than 16,500wppm, less than 16,000wppm, less than 15,500wppm, less than 15,000wppm, less than 12,500wppm, less than 10,000wppm, less than 5000wppm, less than 4000wppm, less than 3000wppm, less than 2000wppm, less than 1000wppm, or less than 500wppm. In some aspects, the silver compound is embedded in the polymer formed by the polymer composition.

[0116] The composition of the silver compound is not particularly limited. Suitable silver compounds include silver iodide, silver bromide, silver chloride, silver fluoride, silver oxide, silver stearate, silver ammonium adipate, silver acetate or silver pyrithione or a combination thereof. The silver compound may include silver oxide, silver ammonium adipate, silver acetate, silver ammonium carbonate, silver stearate, silver phenylphosphinate or silver pyrithione or a combination thereof. In some embodiments, the silver compound includes silver oxide, silver ammonium adipate, silver acetate or silver pyrithione or a combination thereof. In some embodiments, the silver compound includes silver oxide, silver stearate or silver ammonium adipate or a combination thereof. In some aspects, silver is provided in the form of silver oxide. In some aspects, silver is not provided by silver phenylphosphinate and / or silver phenylphosphonate. In some aspects, silver is provided by dissolving one or more silver compounds in ammonium adipate.

[0117] The polymer composition may include phosphorus (in a phosphorus compound), such as phosphorus or a phosphorus compound dispersed in the polymer composition. In one embodiment, the polymer composition includes 50 wppm to 10000 wppm, such as 50 wppm to 5000 wppm, 50 wppm to 2500 wppm, 50 wppm to 2000 wppm, 50 wppm to 800 wppm, 100 wppm to 750 wppm, 100 wppm to 1800 wppm, 100 wppm to 10000 wppm, 100 wppm to 5000 wppm, 100 wppm to 2500 wppm, 100 wppm to 10 ... wppm, 300wppm to 10000wppm, 300wppm to 5000wppm, 300wppm to 2500wppm, 300wppm to 500wppm, 500wppm to 10000wppm, 500wppm to 5000wppm, or 500wppm to 2500wppm. In terms of lower limits, the polymer composition may include greater than 50wppm of phosphorus, such as greater than 75wppm, greater than 100wppm, greater than 150wppm, greater than 200wppm, greater than 300wppm, or greater than 500wppm. In terms of upper limits, the polymer composition can comprise less than 10000 wppm (or 1 wt%), e.g., less than 5000 wppm, less than 2500 wppm, less than 2000 wppm, less than 1800 wppm, less than 1500 wppm, less than 1000 wppm, less than 800 wppm, less than 750 wppm, less than 500 wppm, less than 475 wppm, less than 450 wppm, less than 400 wppm, less than 350 wppm, less than 300 wppm, less than 250 wppm, less than 200 wppm, less than 150 wppm, less than 100 wppm, less than 50 wppm, less than 25 wppm, or less than 10 wppm.

[0118] In some aspects, phosphorus or a phosphorus compound is embedded in a polymer formed from the polymer composition.As described above, due to the overall composition of the disclosed compositions, low amounts (if any) of phosphorus can be used, which can provide advantageous performance results in some cases (see above).

[0119] The phosphorus of polymer composition is present in phosphorus compound or provided by phosphorus compound, and phosphorus compound can be very different.Phosphorus compound can include phenylphosphinic acid, diphenylphosphinic acid, sodium phenylphosphinate (sodiumphenylphosphinate), phosphorous acid, phenylphosphine acid, calcium phenylphosphinate, potassium B-amylphosphinate, methylphosphinic acid, manganese hypophosphite, sodium hypophosphite, monosodium phosphate, hypophosphorous acid, dimethylphosphinic acid, ethylphosphinic acid, diethylphosphinic acid, magnesium ethylphosphinate, triphenyl phosphite, diphenyl methyl phosphite, dimethylphenyl phosphite, ethyl diphenyl phosphite, phenylphosphonic acid, methylphosphonic acid, ethylphosphonic acid, potassium phenylphosphonate, sodium methylphosphonate, calcium ethylphosphonate and combination thereof.In some embodiments, phosphorus compound includes phosphoric acid, phenylphosphinic acid or phenylphosphine acid or combination thereof.In some embodiments, phosphorus compound includes phenylphosphinic acid, phosphorous acid or manganese hypophosphite or combination thereof.In some aspects, phosphorus compound can include phenylphosphinic acid.

[0120] Advantageously, it has been found that the addition of the zinc compound and optionally the phosphorus compound specified above can bring about a beneficial relative viscosity (RV) of the polymer composition. In some embodiments, the RV of the polymer composition is from 5 to 100, e.g., from 5 to 80, 5 to 70, 10 to 70, 15 to 65, 20 to 60, 30 to 50, 35 to 45, 10 to 35, 10 to 20, 60 to 70, 50 to 80, 40 to 50, 30 to 60, 5 to 30, or 15 to 32. In terms of lower limits, the RV of the polymer composition can be greater than 5, e.g., greater than 10, greater than 15, greater than 20, greater than 25, greater than 27.5, greater than 30, greater than 35, greater than 37.5, greater than 40, or greater than 50. In terms of upper limits, the RV of the polymer composition can be less than 100, e.g., less than 90, less than 80, less than 70, less than 65, less than 60, less than 50, less than 45, less than 42.5, less than 40, or less than 35.

[0121] To calculate the RV, the polymer is dissolved in a solvent (usually formic acid or sulfuric acid), the viscosity is measured, and then the viscosity is compared to the viscosity of the pure solvent. This gives a unitless measurement. Solid materials as well as liquids may have a specific RV. Fibers / fabrics made from the polymer composition may also have the above relative viscosities.

[0122] Additional components

[0123] In some embodiments, the polymer composition may contain additional additives. Additives include pigments, hydrophilic or hydrophobic additives, anti-odor additives, additional antiviral agents, and antimicrobial / antifungal inorganic compounds such as copper, zinc, tin, and silver.

[0124] In some embodiments, the polymer composition can be combined with colored pigments for the coloring of fabrics or other components formed by the polymer composition. In some respects, the polymer composition can be combined with ultraviolet additives to withstand fading and degradation in fabrics exposed to significant ultraviolet rays. In some respects, the polymer composition can be combined with additives that make the fiber surface hydrophilic or hydrophobic. In some respects, the polymer composition can be combined with hygroscopic materials, such as to make the fiber, fabric or other products formed therefrom more hygroscopic. In some respects, the polymer composition can be combined with additives that make fabrics flame retardant or fireproof. In some respects, the polymer composition can be combined with additives that make fabrics stain-resistant. In some respects, the polymer composition can be combined with pigments containing antimicrobial compounds so that conventional dyeing and disposal dyes are not required.

[0125] In some embodiments, the polymer composition may further include additional additives. For example, the polymer composition may include a matting agent. Matting agent additives can improve the appearance and / or texture of synthetic fibers and fabrics made from the polymer composition. In some embodiments, inorganic pigment materials can be used as matting agents. The matting agent can include one or more of titanium dioxide, barium sulfate, barium titanate, zinc titanate, magnesium titanate, calcium titanate, zinc oxide, zinc sulfide, lithopone, zirconium dioxide, calcium sulfate, barium sulfate, aluminum oxide, thorium oxide, magnesium oxide, silicon dioxide, talc, mica, etc. In a preferred embodiment, the matting agent includes titanium dioxide. It has been found that polymer compositions including matting agents containing titanium dioxide are made into synthetic fibers and fabrics that are very similar to natural fibers and fabrics, such as synthetic fibers and fabrics with improved appearance and / or texture. It is believed that titanium dioxide improves appearance and / or texture by interacting with zinc compounds, phosphorus compounds and / or functional groups in polymers.

[0126] In one embodiment, the polymer composition comprises a matting agent in an amount of 0.0001 wt % to 3 wt %, e.g., 0.0001 wt % to 2 wt %, 0.0001 to 1.75 wt %, 0.001 wt % to 3 wt %, 0.001 wt % to 2 wt %, 0.001 wt % to 1.75 wt %, 0.002 wt % to 3 wt %, 0.002 wt % to 2 wt %, 0.002 wt % to 1.75 wt %, 0.005 wt % to 3 wt %, 0.005 wt % to 2 wt %, 0.005 wt % to 1.75 wt %. In terms of upper limits, the polymer composition may comprise less than 3 wt % matting agent, e.g., less than 2.5 wt %, less than 2 wt %, or less than 1.75 wt %. In terms of lower limits, the polymer composition can include greater than 0.0001 wt % of the matting agent, eg, greater than 0.001 wt %, greater than 0.002 wt %, or greater than 0.005 wt %.

[0127] In some embodiments, the polymer composition may further comprise a colored material, such as carbon black, copper phthalocyanine pigment, lead chromate, iron oxide, chromium oxide, and ultramarine blue.

[0128] In some embodiments, the polymer composition may include an additional antiviral agent different from zinc. The additional antiviral agent can be any suitable antiviral agent. Conventional antiviral agents are known in the art and can be incorporated into the polymer composition as an additional antiviral agent. For example, the additional antiviral agent can be an entry inhibitor, a reverse transcriptase inhibitor, a DNA polymerase inhibitor, an m-RNA synthesis inhibitor, a protease inhibitor, an integrase inhibitor or an immunomodulator or a combination thereof. In some aspects, an additional antimicrobial agent is added to the polymer composition.

[0129] In some embodiments, the polymer composition may include an additional antimicrobial agent other than zinc. The additional antimicrobial agent can be any suitable antimicrobial agent, such as silver, copper, and / or gold in metallic form (e.g., microparticles, alloys, and oxides), salts (e.g., sulfates, nitrates, acetates, citrates, and chlorides), and / or ionic form. In some aspects, additional additives, such as additional antimicrobial agents, are added to the polymer composition.

[0130] In some embodiments, the polymer composition (and the fibers or fabrics formed therefrom) may further comprise an antimicrobial or antiviral coating. For example, the fibers or fabrics formed from the polymer composition may include a coating of zinc nanoparticles (e.g., nanoparticles of zinc oxide, zinc ammonium adipate, zinc acetate, zinc ammonium carbonate, zinc stearate, zinc phenylphosphinate, or zinc pyrithione, or a combination thereof). In order to produce such a coating, the surface of the polymer composition (e.g., the surface of the fiber and / or fabric formed therefrom) may be cationized and coated layer by layer by gradually immersing the polymer composition in an anionic polyelectrolyte solution (e.g., containing poly-4-styrene sulfonic acid) and a solution containing zinc nanoparticles. Optionally, the coated polymer composition may be hydrothermally treated in a solution of NH4OH at 9°C for 24 hours to fix the zinc nanoparticles.

[0131] In some cases, the AM / AV materials described herein can be effective without the use or inclusion of an acid, such as citric acid and / or acid treatment. Such treatments are known to cause static charge / static decay problems. Advantageously, the need for acid treatment is eliminated, thereby eliminating the static charge / static decay problems associated with conventional configurations.

[0132] Metal retention rate

[0133] As described above, the AM / AV materials described herein have permanent, such as near-permanent, antimicrobial and / or antiviral properties. The permanence of these properties enables the AM / AV materials to be reused, such as after washing, to further extend the utility of the article.

[0134] One indicator for evaluating the permanence, e.g., near-permanence, of the antimicrobial and / or antiviral properties of an AM / AV material is metal retention. As discussed above, the AM / AV material can be prepared from the disclosed polymer composition, which can include various metal compounds, e.g., zinc compounds, phosphorus, copper compounds, and / or silver compounds. The metal compound of the polymer composition can provide antimicrobial and / or antiviral properties to the AM / AV material. Thus, for example, after one or more wash cycles, the retention of the metal compound can provide permanent, e.g., near-permanent, antimicrobial and / or antiviral properties.

[0135] Beneficially, AM / AV materials formed from the disclosed polymer compositions exhibit relatively high metal retention. The metal retention may relate to the retention of a specific metal in the polymer composition, such as zinc retention, copper retention, or to the retention of all metals in the polymer composition, such as total metal retention.

[0136] As discussed above, it has been found that alkali treatment for mercerization will improve the effectiveness of the AM / AV compound to improve overall performance. In some cases, the effectiveness is improved when the zinc content is kept constant or substantially constant. In some cases, the effectiveness is improved when the zinc content is reduced.

[0137] In some embodiments, the AM / AV material formed from the disclosed polymer composition has a metal retention greater than 65% as measured by the dye bath test, for example, greater than 75%, greater than 80%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, greater than 99%, greater than 99.9%, greater than 99.99%, greater than 99.999%, greater than 99.9999%, greater than 99.99999%, or greater than 99.999999%. In terms of upper limits, the AM / AV material may have a metal retention of less than 100%, for example, less than 99.9%, less than 98%, or less than 95%. In terms of ranges, the AM / AV material may have a range of 60% to 100%, for example, 60% to 99.99999%, 60% to 99.99999%, 60% to 99.9999%, 60% to 99.9999%, 60% to 99.999%, 60% to 99.999%, 60% to 99.999%, 60% to 99.99%, 60% to 99%, 60% to 99%, 60% to 98%, 60% to 95%, 65% to 99.9 ... to 99.99999%, 65% to 99.9999%, 65% to 99.999%, 65% to 99.999%, 65% to 100%, 65% to 99.99%, 65% to 99.99%, 65% to 99%, 65% to 99%, 65% to 98%, 65% to 95%, 70% to 100%, 70% to 99.99999%, 70% to 99.99999%, 70% to 99.99999%, 70% to 99.99999%, 70% to 99.999%, 70% to 99.999%, 70% to 99.99%, 70% to 99.9%, 70% to 99%, 70% to 99%, 70% to 98%, 70% to 95%, 75% to 100%, 75% to 99.99%, 75% to 99.99%, 75% to 99.99999%, 75% to 99.99999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, 75% to 99.9999%, .999%, 75% to 99%, 75% to 98%, 75% to 95%, 80% to 99.99999%, 80% to 99.99999%, 80% to 99.99999%, 80% to 99.9999%, 80% to 99.9999%, 80% to 99.9999%, 80% to 100%, 80% to 99.99%, 80% to 99.9%, 80% to 99%, 80% to 98%, or 80% to 95% metal retention. In some cases, ranges and limits relate to dye formulations with lower pH values, such as less than (and / or including) 5.0, less than 4.7, less than 4.6, or less than 4.5. In some cases, ranges and limits relate to dye formulations having higher pH values, such as greater than (and / or including) 4.0, greater than 4.2, greater than 4.5, greater than 4.7, greater than 5.0, or greater than 5.2.

[0138] In some embodiments, the AM / AV material formed from the disclosed polymer composition has a metal retention rate of greater than 40% after dyebath, such as greater than 44%, greater than 45%, greater than 50%, greater than 55%, greater than 60%, greater than 65%, greater than 70%, greater than 75%, greater than 80%, greater than 90%, greater than 95%, or greater than 99%. In terms of upper limits, the AM / AV material can have a metal retention rate of less than 100%, such as less than 99.9%, less than 98%, less than 95%, or less than 90%. In terms of ranges, the AM / AV material can have a metal retention rate of 40% to 100%, such as 45% to 99.9%, 50% to 99.9%, 75% to 99.9%, 80% to 99%, or 90% to 98%. In some cases, ranges and limits relate to dye formulations having higher pH values, such as greater than (and / or including) 4.0, greater than 4.2, greater than 4.5, greater than 4.7, greater than 5.0, or greater than 5.2.

[0139] In some embodiments, the AM / AV material formed by the polymer composition has a metal retention greater than 20%, such as greater than 24%, greater than 25%, greater than 30%, greater than 35%, greater than 40%, greater than 45%, greater than 50%, greater than 55%, or greater than 60%. In terms of upper limits, the AM / AV material may have a metal retention of less than 80%, such as less than 77%, less than 75%, less than 70%, less than 68%, or less than 65%. In terms of ranges, the AM / AV material may have a metal retention of 20% to 80%, such as 25% to 77%, 30% to 75%, or 35% to 70%. In some cases, ranges and limits relate to dye formulations with lower pH values, such as less than (and / or including) 5.0, less than 4.7, less than 4.6, or less than 4.5.

[0140] In other words, in some embodiments, the AM / AV material formed from the polymer composition exhibits a metal compound leaching rate of less than 35%, such as less than 25%, less than 20%, less than 10%, or less than 5%, as measured by the dye bath test. In terms of upper limits, the AM / AV material may exhibit a metal compound leaching rate of greater than 0%, such as greater than 0.1%, greater than 2%, or greater than 5%. In terms of ranges, the AM / AV material can exhibit a metal compound leaching rate of 0% to 35%, e.g., 0% to 25%, 0% to 20%, 0% to 10%, 0% to 5%, 0.1% to 35%, 0.1% to 25%, 0.1% to 20%, 0.2% to 10%, 0.1% to 5%, 2% to 35%, 2% to 25%, 2% to 20%, 2% to 10%, 2% to 5%, 5% to 35%, 5% to 25%, 5% to 20%, or 5% to 10%.

[0141] The metal retention of AM / AV materials can be measured by a dyebath test according to the following standard procedure. The sample is cleaned (all oil removed) by a scour method. The scour method can use a heated bath, for example, at 71° C. for 15 minutes. A wash solution containing 0.25% of a Sterox (723 Soap) nonionic surfactant based on fiber weight (“owf”) and 0.25% owf of TSP (trisodium phosphate) can be used. The sample is then rinsed with cold water.

[0142] The cleaned samples can be tested according to the chemical dye level procedure. This procedure can place them in a dye bath containing 1.0% owf CIAcid Blue 45, 4.0% owf MSP (monosodium phosphate) and % owf disodium phosphate or TSP sufficient to achieve pH 6.0, with a liquid / sample ratio of 28:1. For example, if a pH less than 6 is required, a 10% solution of the required acid can be added using a dropper until the required pH is achieved. The dye bath can be pre-set to boil the bath at 100°C. The sample is placed in the bath for 1.5 hours. As an example, it may take about 30 minutes to reach boiling and keep at this temperature for 1 hour after boiling. Then remove the sample from the bath and rinse. The sample is then transferred to a centrifuge to extract water. After extracting water, the sample is spread out to dry. The component amount is then recorded.

[0143] In some embodiments, the metal retention of the fiber formed by the polymer composition can be calculated by measuring the metal before and after the dye bath operation. The amount of metal retained after the dye bath can be measured by known methods. For the dye bath, an Ahiba dyeing machine (from Datacolor) can be used. In certain cases, 20 grams of undyed fabrics and 200 milliliters of dye liquor can be placed in a stainless steel tank, the pH can be adjusted to the desired level, and the stainless steel tank can be loaded into the dyeing machine; the sample can be heated to 40°C and then heated to 100°C (optionally at 1.5°C / minute). A temperature profile can be used in some cases, such as 1.5°C / minute to 60°C, 1°C / minute to 80°C, and 1.5°C / minute to 100°C. The sample can be kept at 100°C for 45 minutes, then cooled to 40°C with 2°C / minute, then rinsed and dried to obtain a dyed product.

[0144] Methods of forming fibers and nonwovens

[0145] As described above, fibers or fabrics of AM / AV materials are made by forming the AM / AV polymer composition into fibers and arranging the fibers to form a fabric or structure.

[0146] In some aspects, fibers, such as polyamide fibers, are manufactured by spinning a polyamide composition formed in a melt polymerization process. During the melt polymerization process of the polyamide composition, an aqueous monomer solution, such as a salt solution, is heated under controlled conditions of temperature, time, and pressure to evaporate water and achieve polymerization of the monomers to produce a polymer melt. During the melt polymerization process, sufficient zinc and optionally phosphorus are used in the aqueous monomer solution to form a polyamide mixture before polymerization. Monomers are selected based on the desired polyamide composition. After the presence of zinc and phosphorus in the aqueous monomer solution, the polyamide composition can be polymerized. The polymerized polyamide can then be spun into fibers, such as by melt, solution, centrifugal, or electrostatic spinning.

[0147] In some embodiments, a method of preparing a fiber having permanent AM / AV properties from a polyamide composition comprises preparing an aqueous monomer solution, adding less than 20,000 wppm of one or more metal compounds dispersed in the aqueous monomer solution, such as less than 17,500 wppm, less than 17,000 wppm, less than 16,500 wppm, less than 16,000 wppm, less than 15,500 wppm, less than 15,000 wppm, less than 12,500 wppm, less than 10,000 wppm, less than 5000 wppm, less than 4000 wppm, less than 3000 wppm, less than 2000 wppm, less than 1000 wppm, or less than 500 wppm, polymerizing the aqueous monomer solution to form a polymer melt, and spinning the polymer melt to form AM / AV fibers. In this embodiment, the polyamide composition comprises the aqueous monomer solution obtained after adding the metal compound.

[0148] In some embodiments, the method includes preparing an aqueous monomer solution. The aqueous monomer solution may include amide monomers. In some embodiments, the monomer concentration in the aqueous monomer solution is less than 60 weight %, such as less than 58 weight %, less than 56.5 weight %, less than 55 weight %, less than 50 weight %, less than 45 weight %, less than 40 weight %, less than 35 weight % or less than 30 weight %. In some embodiments, the monomer concentration in the aqueous monomer solution is greater than 20 weight %, such as greater than 25 weight %, greater than 30 weight %, greater than 35 weight %, greater than 40 weight %, greater than 45 weight %, greater than 50 weight %, greater than 55 weight % or greater than 58 weight %. In some embodiments, the monomer concentration in the aqueous monomer solution is in the range of 20 weight % to 60 weight %, such as 25 weight % to 58 weight %, 30 weight % to 56.5 weight %, 35 weight % to 55 weight %, 40 weight % to 50 weight %, or 45 weight % to 55 weight %. The remainder of the aqueous monomer solution may include water and / or additional additives. In some embodiments, the monomers comprise amide monomers, including a diacid and a diamine, ie, a nylon salt.

[0149] In some embodiments, the monomer aqueous solution is a nylon salt solution. Nylon salt solutions can be formed by mixing diamines and diacids with water. For example, water, diamines and dicarboxylic acid monomers are mixed to form a salt solution, such as adipic acid and hexamethylenediamine are mixed with water. In some embodiments, the diacid can be a dicarboxylic acid and can be selected from oxalic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, adipic acid, suberic acid, azelaic acid, sebacic acid, undecane diacid, dodecanedioic acid, maleic acid, glutaconic acid, callous acid and hexanedioic acid, 1,2- or 1,3-cyclohexanedicarboxylic acid, 1,2- or 1,3-phenylenedioic acid, 1,2- or 1,3-cyclohexanediacetic acid, isophthalic acid, terephthalic acid, 4,4'-oxybisbenzoic acid, 4,4-benzophenone dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, p-tert-butylisophthalic acid and 2,5-furan dicarboxylic acid and mixtures thereof. In some embodiments, the diamine may be selected from ethanol diamine, trimethylene diamine, putrescine, cadaverine, hexamethylene diamine, 2-methylpentamethylene diamine, heptamethylene diamine, 2-methylhexamethylene diamine, 3-methylhexamethylene diamine, 2,2-dimethylpentamethylene diamine, octanediamine, 2,5-dimethylhexamethylene diamine, nonamethylene diamine, 2,2,4- and 2,4,4-trimethylhexamethylene diamine, decanediamine, 5-methylnonane diamine, isophorone diamine, undecamethylene diamine, dodecamethylene diamine, 2,2,7,7-tetramethyloctanediamine, bis(p-aminocyclohexyl)methane, bis(aminomethyl)norbornane, C2-C16 aliphatic diamines optionally substituted with one or more C1 to C4 alkyl groups, aliphatic polyether diamines and furanediamines, such as 2,5-bis(aminomethyl)furan and mixtures thereof. In a preferred embodiment, the diacid is adipic acid and the diamine is hexamethylene diamine, which polymerize to form PA6,6.

[0150] It should be understood that the concept of producing polyamides from diamines and diacids also includes other suitable monomers, such as the concept of amino acids or lactams. Without limiting the scope, the example of amino acids may include 6-aminocaproic acid, 7-aminoheptanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid or a combination thereof. Without limiting the scope of the present disclosure, the example of lactams may include caprolactam, enantholactam, lauryl lactam or a combination thereof. Suitable feeds for the method of the present disclosure may include a mixture of diamines, diacids, amino acids and lactams.

[0151] After preparing the monomer aqueous solution, a metal compound (e.g., a zinc compound, a copper compound, and / or a silver compound) is added to the monomer aqueous solution to form a polyamide composition. In some embodiments, less than 20,000 wppm of the metal compound is dispersed in the monomer aqueous solution. In some aspects, additional additives, such as additional AM / AV agents, are added to the monomer aqueous solution. Optionally, phosphorus (e.g., a phosphorus compound) is added to the monomer aqueous solution.

[0152] In some cases, the polyamide composition is polymerized using a conventional melt polymerization process. In one aspect, the aqueous monomer solution is heated under controlled conditions of time, temperature and pressure to evaporate water, achieve monomer polymerization and provide a polymer melt. In some aspects, a specific weight ratio of zinc to phosphorus can advantageously promote zinc incorporation into the polymer, reduce thermal degradation of the polymer and enhance its dyeability.

[0153] In one embodiment, nylon is prepared by conventional melt polymerization of a nylon salt. Typically, a nylon salt solution is melted under pressure (e.g., 250 psig / 1825×10 3 n / m 2 ) to a temperature of, for example, about 245° C. The water vapor is then vented by reducing the pressure to atmospheric pressure while raising the temperature to, for example, about 270° C. Zinc and optionally phosphorus are added to the nylon salt solution prior to polymerization. The resulting molten nylon is maintained at this temperature for a period of time to allow it to reach equilibrium before being extruded into fibers. In some aspects, the process can be carried out in a batch or continuous process.

[0154] In some embodiments, zinc, such as zinc oxide, is added to the aqueous monomer solution during the melt polymerization process. AM / AV fibers may include polyamides made in a melt polymerization process rather than a masterbatch process. In some aspects, the resulting fibers have permanent AM / AV properties. The resulting fibers can be used as topsheet layers and / or padlayers of AM / AV materials.

[0155] The AM / AV agent can be added to the polyamide during the melt polymerization process, for example as a masterbatch or as a powder to polyamide pellets, which can thereafter be spun to form fibers. The fibers can then be formed into a nonwoven structure.

[0156] In some aspects, the AM / AV nonwoven structure is meltblown. Meltblowing is advantageously cheaper than electrospinning. Meltblowing is a type of process developed for forming microfibers and nonwoven webs. Until recently, microfibers were produced by meltblowing. Now, nanofibers can also be formed by meltblowing. Nanofibers are formed by extruding a molten thermoplastic polymer material or polyamide through a plurality of small holes. The resulting molten threads or filaments enter a converging high-speed gas stream, which attenuates or stretches the filaments of the molten polyamide to reduce their diameter. Thereafter, the high-speed gas stream carries the meltblown nanofibers and deposits them on a collecting surface or forming wire to form a nonwoven web of randomly distributed meltblown nanofibers. Forming nanofibers and nonwoven webs by meltblowing is well known in the art. See, for example, U.S. Patent Nos. 3,704,198; 3,755,527; 3,849,241; 3,978,185; 4,100,324; and 4,663,220.

[0157] One option, "islands in the sea", refers to forming fibers by extruding at least two polymer components from a spinning die, also known as conjugate spinning.

[0158] As is well known, many manufacturing parameters of electrospinning may limit the spinning of certain materials. These parameters include: the charge of the spinning material and the spinning material solution; solution delivery (usually the material stream ejected from the ejector); the charge at the jet; the discharge of the fiber membrane on the collector; the external force from the electric field on the spinning jet; the density of the discharged jet; and the (high) voltage of the electrode and the geometry of the collector. In contrast, the above-mentioned nanofibers and products are advantageously not formed using an external electric field as the main ejection force as required in the electrospinning method. Therefore, polyamide and any component of the spinning process are not charged. Importantly, the method / product of the present disclosure does not require the dangerous high voltage necessary in the electrospinning method. In some embodiments, the method is a non-electrospinning method and the resulting product is a non-electrospinning product made by a non-electrospinning method.

[0159] Another embodiment of making nanofiber nonwovens is to use propellant gas via spinning channel two-phase spinning or melt-blowing as described in U.S. Patent No. 8,668,854. This method includes polymer or polymer solution and pressurized propellant gas (usually air) two-phase flow to a thin preferably converging channel. The channel is usually and preferably annularly configured. It is believed that the polymer is sheared by the air flow in the thin preferably converging channel to produce polymer film layers on both sides of the channel. These polymer film layers are further sheared into nanofibers by the propellant air flow. Here, a mobile collecting belt can still be used and the basis weight of the nanofiber nonwoven can be controlled by adjusting the speed of the belt. The fineness of the nanofiber nonwoven can also be controlled by the distance of the collector.

[0160] Beneficially, the use of the polyamide precursors mentioned above in the melt spinning process provides significant benefits in productivity, such as at least 5% higher, at least 10% higher, at least 20% higher, at least 30% higher, at least 40% higher. The improvement can be observed as an improvement in area per hour compared to a conventional method, such as another method that does not use the features described herein. In some cases, the output is increased over a consistent period of time. For example, over a given production period, such as 1 hour, the method of the present disclosure produces at least 5% more product than a conventional method or electrospinning method, such as at least 10% more, at least 20% more, at least 30% more, or at least 40% more.

[0161] Another method that can be used is melt blowing. Melt blowing involves extruding the polyamide into a relatively high velocity, usually hot, gas stream. To produce suitable nanofibers, careful selection of pore and capillary geometry and temperature is required as shown in Hassan et al., J Membrane Sci., 427, 336-344, 2013 and Ellison et al., Polymer, 48 (11), 3306-3316, 2007 and International Nonwoven Journal, Summer 2003, pp. 21-28.

[0162] U.S. Patent No. 7,300,272 (incorporated herein by reference) discloses a fiber extrusion pack for extruding a molten material to form a series of nanofibers, which includes a plurality of split distribution plates arranged in a stack so that each split distribution plate forms a layer within the fiber extrusion assembly, and features on the split distribution plates form a distribution network for delivering molten material to holes in the fiber extrusion assembly. Each split distribution plate includes a set of plate segments, with gaps set between adjacent plate segments. The adjacent edges of the plate segments are molded to form reservoirs along the gaps, and sealing plugs are placed in the reservoirs to prevent molten material from leaking from the gaps. The sealing plugs can be formed by molten material that leaks into the gaps and is collected and solidified in the reservoirs or by placing plugging materials in the reservoirs during assembly of the pack. This assembly can be used together with the meltblowing system described in the previously mentioned patents to manufacture nanofibers. The system and method of U.S. Patent No. 10,041,188 (incorporated herein by reference) are also exemplary.

[0163] In one embodiment, a method for preparing an AM / AV nonwoven polyamide structure is disclosed, which is used, for example, for a fabric sheet. The method comprises the step of forming a (precursor) polyamide (the preparation of a monomer solution is well known), for example, by preparing an aqueous monomer solution. During the precursor preparation process, a metal compound, such as zinc, is added (as discussed herein). In some cases, the metal compound is added to (and dispersed in) the aqueous monomer solution. Phosphorus may also be added. In some cases, the precursor is polymerized to form a polyamide composition. The method further comprises the steps of forming polyamide fibers and forming the AM / AV polyamide fibers into a structure. In some cases, the polyamide composition is melt-spun, spunlace, spunbonded, electrospun, solution-spun, or centrifugally spun. The resulting fiber can be a melt-spun fiber, a spunlace fiber, a spunbonded fiber, an electrospun fiber, a solution-spun fiber, a centrifugally spun fiber, or a staple fiber.

[0164] Fabrics can be made from the fibers by conventional means.

[0165] As used herein, "greater than" and "less than" limits may also include the numbers associated therewith. In other words, "greater than" and "less than" may be interpreted as "greater than or equal to" and "less than or equal to". It is contemplated that the wording may be subsequently modified in a claim to include "or equal to". For example, "greater than 4.0" may be interpreted and subsequently modified in a claim to "greater than or equal to 4.0".

[0166] In some embodiments, any or some of the components or steps disclosed herein may be considered optional. In some cases, the disclosed compositions may explicitly exclude any or some of the above-mentioned components or steps in this specification, such as through the wording of the claims. For example, the wording of the claims may be modified to indicate that the disclosed compositions, materials, methods, etc. do not use or contain one or more of the above-mentioned additives, for example, the disclosed materials do not contain flame retardants or matting agents. As another example, the wording of the claims may be modified to indicate that the disclosed materials do not contain long-chain polyamide components, such as PA-12. Such negative limitations are contemplated, and this text serves as support for negative limitations of components, steps, and / or features. Example

[0167] Nylon / cotton fiber or yarn blends (also commonly referred to as NYCO blends) are prepared using cotton staple fibers and / or polyamide staple fibers. The polyamide staple fibers are formed by typical staple fiber production processes, such as melt extrusion, filament formation, drawing, crimping, and cutting. The formic acid relative viscosity of the fibers / staple fibers is from 20 to 60, such as from 30 to 50. The base polyamide staple fibers of the operating examples are produced using AM / AV polymer compositions comprising PA-66 and various amounts of zinc from 100 wppm to 400 wppm. The base fibers / fabrics of the comparative examples contain only polymer and no zinc.

[0168] The fabric was treated with a 25% sodium hydroxide solution for about 1 minute. The treatment was carried out at a temperature of about 15°C.

[0169] The fabrics were tested for AM / AV efficacy as measured by log reduction of S. aureus and K. pneumoniae (as determined by ISO 20743:2013).

[0170] The compositions and results of Examples and Comparative Examples are shown in Table 1 below.

[0171]

[0172]

[0173] As shown in Table 1, the alkali treated (zinc containing) working examples showed superior performance to the untreated control examples in both log reduction of Klebsiella pneumoniae and Staph Aureus. These examples demonstrate the surprising and synergistic results achieved by the disclosed treatment of the base fabric / fiber (comprising the AM / AV compound) with the alkali composition.

[0174] For example, Exs. 1 and 2 each used a 60 / 40 nylon / cotton blend and were treated with an alkali solution. Ex. 8 used a similar 57 / 43 nylon / cotton blend and was treated with an alkali solution. Comparative Example H also used a 60 / 40 nylon / cotton blend, but without the zinc content and without the alkali solution treatment. Exs. 1, 2, and 8 surprisingly showed 4.8, 5.9, and 7.1 log reductions in Staphylococcus, respectively, while Comparative Example H showed 0 log reduction in Staphylococcus under the same test conditions. Exs. 1, 2, and 8 surprisingly showed 4.0, 8.2, and 7.5 log reductions in Klebsiella, respectively, while Comparative Example H showed 0 log reduction in Klebsiella under the same test conditions.

[0175] Ex.6 also used a 40 / 60 nylon / cotton blend and was treated with an alkali solution. Ex.G also used a 40 / 60 nylon / cotton blend but without the zinc content and was not treated with an alkali solution. Ex.6 surprisingly showed a 4.1 log reduction in Staphylococcus, while Comparative Example G showed a 0 log reduction in Staphylococcus under the same test conditions. Ex.6 surprisingly showed a 7.4 log reduction in Klebsiella, while Comparative Example G showed a 0.1 log reduction in Klebsiella under the same test conditions.

[0176] Ex.3 used a heavy nylon blend (90 / 10) containing 224 ppm zinc and was treated with an alkaline solution. Comparative Example E used a similar blend (all nylon) and a higher zinc content and was not treated with an alkaline solution. Despite the lower zinc content, under the same test conditions, Ex.3 unexpectedly showed a 7.8 log reduction in Staphylococcus, while Comparative Example E showed only a 2.2 log reduction in Staphylococcus. Also, under the same test conditions, Ex.3 unexpectedly showed a 7.4 log reduction in Klebsiella, while Comparative Example E showed only a 2.0 log reduction in Klebsiella. These results were particularly unexpected because Ex.3 used a lower zinc content.

[0177] The Examples are replete with other surprising comparisons to demonstrate the synergistic benefits of the disclosed methods and resulting AM / AV fibers.

[0178] Implementation

[0179] As used hereinafter, any reference to a series of embodiments is understood to be a reference to each of those embodiments individually (eg "embodiments 1-4" is understood to be "embodiment 1, 2, 3 or 4").

[0180] Embodiment 1 is a method of producing an improved, treated AM / AV fiber comprising treating a base fiber, such as a base AM / AV fiber, with an alkaline composition to form an improved, treated AM / AV fiber, wherein the improved, treated AM / AV fiber exhibits a Klebsiella pneumoniae log reduction of greater than 1.5 as determined by ISO 20743:2013.

[0181] Embodiment 2 is the method of embodiment 1, wherein the polymer, for example the base AM / AV fiber, comprises polyamide.

[0182] Embodiment 3 is the method of embodiment 1 or 2, wherein the treating comprises treating the base AM / AV fiber to form a treated AM / AV fiber and treating the companion fiber to form a treated companion fiber, and wherein the companion fiber comprises a natural fiber, preferably cotton and / or cellulose.

[0183] Embodiment 4 is the method of embodiments 1-3, wherein the polymer of the AM / AV fibers comprises polyamide and the polymer of the companion fibers comprises cellulose and / or cotton.

[0184] Embodiment 5 is the method of embodiments 1-4, wherein the mercerizing treatment improves the AM / AV properties of the fiber relative to the base fiber.

[0185] Embodiment 6 is the method of embodiments 1-5, wherein the polymer composition comprises 5 wppm to 20,000 wppm AM / AV compound.

[0186] Embodiment 7 is the method of embodiments 1-6, wherein the improved treated AM / AV fiber exhibits an E. coli log reduction of greater than 1.5 as determined by ASTM E3160 (2018).

[0187] Embodiment 8 is the method of embodiments 1-7, wherein the improved treated AM / AV fiber exhibits a log reduction of Staphylococcus aureus greater than 3.0 as determined by ISO 20743:2013.

[0188] Embodiment 9 is the method of embodiments 1-8, wherein the polymer composition has a relative viscosity of less than 100 as measured by the formic acid method.

[0189] Embodiment 10 is the method of embodiments 1-9, wherein the polymer, for example the base AM / AV fiber, is hydrophilic and / or hygroscopic and is capable of absorbing greater than 1.5 weight percent water based on the total weight of the polymer.

[0190] Embodiment 11 is the method of embodiments 1-10, wherein the polymer, for example, of the base AM / AV fiber comprises PA 6, PA 6,6, PA 6,10 or PA 6,12 or a combination thereof.

[0191] Embodiment 12 is the method of embodiments 1-11, wherein the treating comprises contacting the base AM / AV fiber with an alkaline solution having a concentration of 5% to 50%.

[0192] Embodiment 13 is the method of embodiments 1-12, wherein the treating is performed for a residence time of 5 seconds to 30 minutes.

[0193] Embodiment 14 is the method of embodiments 1-13, wherein the treating is carried out at a temperature of 5°C to 50°C.

[0194] Embodiment 15 is the method of embodiments 1-14, further comprising the step of washing and / or neutralizing the fibers.

[0195] Embodiment 16 is the method of embodiments 1-15, wherein the fiber comprises embedded ionic zinc (Zn 2+ ) of a polyamide polymer matrix.

[0196] Embodiment 17 is the method of embodiments 1-6, wherein the AM / AV base fibers comprise staple fibers.

[0197] Embodiment 18 is a treated AM / AV fiber comprising a polymer and an AM / AV compound, wherein the treated AM / AV fiber is alkali-treated with an alkali composition, wherein the AM / AV fiber exhibits a Klebsiella pneumoniae log reduction of greater than 1.5 as determined by ISO 20743:2013.

[0198] Embodiment 19 is the fiber of embodiment 18, wherein the alkali composition has a concentration of 5% to 50%.

[0199] Embodiment 20 is the fiber of embodiment 18 or 19, wherein the treated AM / AV fiber comprises PA6, PA6,6, PA 6,10 or PA 6,12 or a combination thereof, and wherein the treated AM / AV fiber has a relative viscosity of 20 to 60 as measured by the formic acid method.

Claims

1. A method for producing treated AM / AV fibers, wherein include: treating a base AM / AV fiber, preferably a staple fiber, with an alkaline composition to form a treated AM / AV fiber, the base AM / AV fiber comprising a polymer composition comprising a polymer and an AM / AV compound; wherein the treated AM / AV fibers exhibit a Klebsiella pneumoniae log reduction of greater than 1.5 as determined by ISO 20743:2013.

2. The method according to claim 1, wherein the polymer of the base AM / AV fiber comprises polyamide.

3. The method according to claim 1, wherein the treating comprises treating a base AM / AV fiber to form a treated AM / AV fiber, and treating a companion fiber, preferably comprising a natural fiber, preferably cellulose and / or cotton, to form a treated companion fiber.

4. The method of claim 1, wherein the polymer composition comprises from 5 wppm to 20,000 wppm AM / AV compounds.

5. The method of claim 1, wherein the treated AM / AV fiber exhibits a log reduction of E. coli greater than 1.5 as determined by ASTM E3160 (2018) and / or a log reduction of Staphylococcus aureus greater than 3.0 as determined by ISO 20743:2013.

6. The method according to claim 1, wherein the polymer composition has a relative viscosity of less than 100 as measured by the formic acid method.

7. The method according to claim 1, wherein the polymer of the base AM / AV fiber is hydrophilic and / or hygroscopic and is capable of absorbing more than 1.5 wt. % water, based on the total weight of the polymer.

8. The method according to claim 1, wherein the polymer of the base AM / AV fiber comprises PA6, PA 6,6, PA 6,10 or PA 6,12 or a combination thereof.

9. The method according to claim 1, wherein the treating comprises contacting the base AM / AV fibers with an alkali composition at a concentration of 5% to 50%.

10. The method according to claim 1, wherein the treatment is carried out at a residence time of 5 seconds to 30 minutes and / or at a temperature of 5°C to 50°C.

11. The method of claim 1 further comprising the steps of washing said treated fibers and neutralizing said fibers.

12. The method according to claim 1, wherein the fibers contain zinc ions embedded therein (Zn 2+ ) of a polyamide polymer matrix.

13. A treated AM / AV fiber comprising a polymer and an AM / AV compound, wherein the treated AM / AV fiber is alkali-treated with an alkali composition, wherein the AM / AV fiber exhibits a Klebsiella pneumoniae log reduction of greater than 1.5 as determined by ISO 20743:2013.

14. The treated AM / AV fiber according to claim 13, wherein the alkali composition has a concentration of 5% to 50%.

15. The treated AM / AV fiber according to claim 13, wherein the treated AM / AV fiber comprises PA6, PA6,6, PA 6,10 or PA 6,12 or a combination thereof, and wherein the treated AM / AV fiber has a relative viscosity of 20 to 60 as measured by formic acid method.

Citation Information

Patent Citations

  • Method and apparatus for production of meltblown nanofibers

    US10041188B2

  • Polyamide nanofiber nonwovens

    US10662561B2

  • Antiviral / antimicrobial polymer compositions, fibers, and products

    US12043721B2

  • Stretchable and dimensionally stable woven fabric made from polytrimethylene terephthalate based core spun yarns.

    US20140308865A1

  • Antiviral articles

    US20210274778A1